Surface modified calcium carbonate as a support for transition metal based catalysts

By using the catalyst system that combines surface-reacted calcium carbonate as a support and transition metal compounds, the problems of high catalyst load, large resource consumption and difficult recovery in the prior art are solved, and efficient, environmentally friendly and economical catalytic reactions are achieved.

CN109475849BActive Publication Date: 2025-03-21OMYA INT AG
View PDF 22 Cites 0 Cited by

Patent Information

Application Number
CN201780045749.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-08-01
Filing Date
2017-07-17
Publication Date
2025-03-21
Estimated Expiration
2037-07-17

AI Technical Summary

Technical Problem

The existing transition metal catalyst system has problems such as high catalyst load, large conversion of transition metals, scarce resources and high procurement costs, and it is difficult to achieve efficient recycling and environmentally friendly catalytic reactions.

Method used

The surface-reacted calcium carbonate is used as a solid support, and the reaction of natural calcium carbonate or precipitated calcium carbonate with CO2 and H3O+ ion donors is formed. Combined with water-insoluble calcium salts, a catalyst system with a high specific surface area and a suitable pore volume is formed, and a catalyst is formed with contact with the transition metal compound.

Benefits of technology

It achieves reducing catalyst loading and transition metal consumption, improving catalytic activity and turnover rate, making it easier to recover, and is more environmentally friendly and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0001954902150000331
    Figure BDA0001954902150000331
  • Figure BDA0001954902150000351
    Figure BDA0001954902150000351
  • Figure BDA0001954902150000361
    Figure BDA0001954902150000361
Patent Text Reader

Abstract

The present invention relates to a catalyst system comprising a transition metal compound on a solid support, the solid support being a "surface-reacted calcium carbonate" comprising calcium carbonate and a water-insoluble calcium salt other than calcium carbonate, such as hydroxyapatite. The present invention also relates to a process for the manufacture of the catalyst system and its use in heterogeneous catalysis, in particular in C-C cross-coupling and glycerol hydrogenolysis.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a catalyst system comprising a transition metal compound on a solid support, the solid support being a surface-reacted calcium carbonate, and a method for producing the catalyst system. The present invention also relates to the use of the catalyst system in pellets or moldings. The catalyst system and the corresponding pellets or moldings can be used for various transition metal-catalyzed reactions.

[0002] Combined support / catalyst systems are widely used in heterogeneous catalysis and have several advantages. For example, such catalyst systems are less expensive to handle and to separate the reaction products than conventional homogeneous systems. In addition, the activity and efficiency of the catalyst system in a given reaction can be controlled by selecting the specific structural characteristics of the support.

[0003] Elemental transition metals and corresponding compounds such as transition metal salts or complexes are well-known catalysts and can be used in many reactions, for example for the hydrogenation of olefins or alkynes or for epoxidation. The most frequently used transition metals include platinum, palladium and copper.

[0004] Commonly used support materials for heterogeneous transition metal catalysis are activated carbon, carbon black / graphite, alumina, barium sulfate and calcium carbonate (The Catalyst Technical Handbook, Johnson Matthey Co., 2005).

[0005] For example, US Pat. Nos. 5,965,480 and 5,703,254 disclose the direct oxidation of propylene to propylene oxide using a silver catalyst on a support containing an alkaline earth metal carbonate, such as calcium carbonate, to selectively catalyze the formation of the epoxide.

[0006] WO 2004 / 030813 A1 relates to a method for preparing a catalyst, comprising: (a) preparing a paste having a homogeneous mixture of at least one alkaline earth metal carbonate, a liquid medium, a silver binding additive and at least one extrusion aid and / or an optional burnout additive; (b) forming one or more shaped particles from the paste; (c) drying and calcining the particles; and (e) impregnating the dried and calcined particles with a solution comprising a silver compound. The alkaline earth metal carbonate may be calcium carbonate.

[0007] WO 96 / 01242 A1 discloses a method for selectively hydrogenating 1,4-butynediol to 1,4-butenediol using a palladium catalyst, wherein copper and zinc or silver and zinc are added as dopants. The catalyst can be provided on a solid support. The support material can be calcium carbonate, such as precipitated calcium carbonate.

[0008] WO 2013 / 190076 A1 relates to a catalytic system, which is a Lindlar-type catalyst, wherein the average particle size (d 50 ) is greater than 10 μm. It also discloses the use of this catalytic system for partially hydrogenating carbon-carbon triple bonds into double bonds. Specific examples of support materials include precipitated calcium carbonate.

[0009] However, the toxicity of transition metals and corresponding salts is a common disadvantage, so the catalyst loading in transition metal-catalyzed reactions should be kept as low as possible. Another disadvantage of transition metals can be seen in: the scarce availability of natural resources; and, if possible at all, the high cost of procurement and recycling. Therefore, there is a constant need to improve catalyst systems to overcome one or more of the above-mentioned disadvantages.

[0010] One object of the present invention can therefore be seen in providing a more efficient catalyst system which allows reducing the catalyst loading and the overall consumption of transition metal during catalysis.

[0011] Another object of the present invention can be seen in providing a time-saving catalyst system with a higher turnover rate.

[0012] Yet another object can be seen in providing a catalyst system that can be easily recycled in order to reduce the overall consumption of transition metals.

[0013] A further object can therefore be seen in providing catalyst systems which are more environmentally compatible.

[0014] Finally, another object of the present invention can be seen in providing a more cost-effective catalytic reaction system.

[0015] The above-mentioned and other problems may be solved by the subject matter as defined herein in the independent claims.

[0016] In this respect, a first aspect of the invention relates to a catalyst system comprising a transition metal compound on a solid support, wherein the solid support is a surface-reacted calcium carbonate comprising ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) and at least one water-insoluble calcium salt other than calcium carbonate, and wherein the surface-reacted calcium carbonate exhibits:

[0017] (i) 15 m³ measured using nitrogen and the BET method according to ISO 9277:2010 2 / g to 200m 2 / g specific surface area;

[0018] (ii) The pore size at 0.1 cm calculated from mercury porosimetry measurements 3 / g to 2.3cm 3 / g range of intrusion specific pore volume within the particle; and

[0019] (iii) a ratio of at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite in the range of 1:99 to 99:1.

[0020] The inventors of the present application unexpectedly discovered that the use of surface-reacted calcium carbonate (SRCC) as a catalyst support in transition metal catalysis provides several advantages. The surface-reacted calcium carbonate is a catalytic catalyst that has been reacted with CO2 and one or more H3O + The reaction product of ion donor treated ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) wherein CO2 is reacted with H3O + The ion donor is formed in situ. Additionally or alternatively, CO2 can be supplied from an external source. Since the GNCC or PCC is combined with CO2 and one or more H3O + The SRCC comprises ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) and at least one water-insoluble calcium salt other than calcium carbonate produced by the above reaction. The material has specific surface properties and is unexpectedly found to be useful as a support material in heterogeneous catalysis.

[0021] For example, higher conversions in CC cross-coupling reactions and higher catalytic activities in glycerol hydrogenolysis are achieved with the catalyst system according to the invention. In addition, the catalyst system according to the invention is easier to recycle and achieves higher yields, for example, in the second catalytic cycle, compared to conventional support systems.

[0022] Another aspect of the present invention relates to a method for making a catalyst system comprising a transition metal compound on a solid support, the method comprising the steps of:

[0023] (a) providing at least one surface-reacted calcium carbonate comprising ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) and at least one water-insoluble calcium salt other than calcium carbonate;

[0024] (b) providing at least one transition metal compound; and

[0025] (c) contacting the surface-reacted calcium carbonate provided in step (a) with the transition metal compound provided in step (b) in a liquid medium to obtain a mixture comprising surface-reacted calcium carbonate and the transition metal compound;

[0026] The surface-reacted calcium carbonate showed:

[0027] (i) 15 m³ measured using nitrogen and the BET method according to ISO 9277:2010 2 / g to 200m 2 / g specific surface area;

[0028] (ii) The pore size at 0.1 cm calculated from mercury porosimetry measurements 3 / g to 2.3cm 3 / g range of intrusion specific pore volume within the particle; and

[0029] (iii) a ratio of at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite in the range of 1:99 to 99:1.

[0030] A further aspect of the present invention relates to the catalyst system of the present invention obtainable according to the process described above.

[0031] Yet another aspect of the present invention relates to the use of the catalyst system in a process comprising the following steps:

[0032] (a) providing one or more reactants;

[0033] (b) providing the catalyst system of the present invention;

[0034] (c) subjecting the one or more reactants provided in step (a) to a chemical reaction in the presence of the catalyst system provided in step (b).

[0035] Yet another aspect of the present invention relates to the use of the surface-reacted calcium carbonate as described herein as a support for a transition metal based catalyst.

[0036] Finally, a further aspect of the present invention relates to pellets, moldings or extrudates comprising the catalyst system according to the invention.

[0037] It should be understood that for the purposes of the present invention, the following terms shall have the following meanings:

[0038] In the meaning of the present invention, "ground natural calcium carbonate" (GNCC) is calcium carbonate obtained from natural sources such as limestone, marble or chalk and processed by wet and / or dry treatments such as grinding, sieving and / or classifying (e.g. by cyclones or classifiers).

[0039] In the meaning of the present invention, "precipitated calcium carbonate" (PCC) is a synthetic material, which is generally obtained by precipitation after reacting carbon dioxide and calcium hydroxide (slaked lime) in an aqueous environment or by precipitation in water by a calcium source and a carbonate source. In addition, precipitated calcium carbonate can also be the product of introducing calcium salts and carbonates (e.g., calcium chloride and sodium carbonate) into an aqueous environment. PCC can have vaterite, calcite or aragonite crystal forms. PCC is described in, for example, EP 2 447 213 A1, EP 2 524 898 A1, EP 2 371 766 A1, EP 2 840 065 A1 or WO 2013 / 142473 A1.

[0040] The "surface-reacted calcium carbonate" according to the present invention is a calcium carbonate reacted with CO2 and one or more H3O + The reaction product of ion donor treated ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) wherein CO2 is reacted with H3O + The ion donor process is formed in situ and / or supplied from an external source. In the context of the present invention, H3O + Brønsted Acids and / or acid salts.

[0041] The "particle size" of the surface-reacted calcium carbonate herein is described as the particle size distribution based on volume. x (volume). Among them, the value d x (volume) represents the diameter at which x volume % of the particles have a diameter smaller than d x (volume). This means, for example, that d 20 The (volume) value is the particle size that is smaller than 20% by volume of all particles. 50 The (volume) value is the volume median particle size, i.e., the particle size that is smaller than 50% by volume of all particles; d 98 The (volume) value is the particle size below which 98% by volume of all particles are smaller than.

[0042] The "particle size" of a particulate material other than surface-reacted calcium carbonate herein is defined by its particle size distribution d x (weight). Among them, the value d x (weight) represents the diameter at which x weight % of the particles have a diameter smaller than d x (weight). This means, for example, that d 20 The (weight) value is the particle size below which 20% by weight of all particles are smaller than. 50 The (weight) value is the weight median particle size, ie, the particle size below which 50% by weight of all particles are smaller.

[0043] Throughout this document, the “specific surface area” (in m2) of surface-reacted calcium carbonate or other materials is 2 The adsorption capacity (wt. / g) is determined using the BET method (using nitrogen as adsorption gas) which is well known to the skilled person (ISO 9277:2010).

[0044] For the purposes of the present invention, "porosity" or "pore volume" refers to the intrusion-specific pore volume within a particle. The porosity or pore volume is measured using a Micromeritics Autopore V 9620 mercury porosimeter.

[0045] A "water-insoluble" material is defined as a material that, when 100 g of said material is mixed with 100 g of deionized water and filtered at 20°C on a filter having a pore size of 0.2 μm to recover a liquid filtrate, provides less than or equal to 1 g of recovered solid material upon evaporation of 100 g of said liquid filtrate at 95°C to 100°C at ambient pressure. Thus, a "water-soluble" material is defined as a material that, when 100 g of said material is mixed with 100 g of deionized water and filtered at 20°C on a filter having a pore size of 0.2 μm to recover a liquid filtrate, provides greater than 1 g of recovered solid material upon evaporation of 100 g of said liquid filtrate at 95°C to 100°C at ambient pressure.

[0046] A "suspension" or "slurry" within the meaning of the present invention comprises insoluble solids and a liquid medium (eg water) and optionally also additives, and generally contains a large amount of solids and is therefore more viscous and possibly denser than the liquid from which it is formed.

[0047] The term "solid" according to the present invention refers to a material that is solid at standard ambient temperature and pressure (SATP), which refers to a temperature of 298.15 K (25° C.) and an absolute pressure of exactly 1 bar. The solid may be in the form of a powder, a sheet, a granule, a flake, etc. Thus, the term "liquid medium" refers to a material that is liquid at standard ambient temperature and pressure (SATP), which refers to a temperature of 298.15 K (25° C.) and an absolute pressure of exactly 1 bar.

[0048] When the term "comprising" is used in the present description and claims, it does not exclude other unspecified elements of major or minor functional importance. For the purposes of the present invention, the term "consisting of" is considered to be a preferred embodiment of the term "comprising". If a group is defined hereinafter as comprising at least a certain number of embodiments, it is also understood to disclose a group that preferably consists only of these embodiments.

[0049] Whenever the terms "including" or "having" are used, these terms are meant to be equivalent to "comprising" as defined above.

[0050] Unless otherwise specifically stated, when referring to a singular noun using an unmodified quantifier, it includes the plural of that noun.

[0051] Terms such as "obtainable" or "definable" and "obtained" or "defined" can be used interchangeably. This means, for example, that unless the context clearly indicates otherwise, the term "obtained" is not meant to indicate, for example, that an embodiment must be obtained by, for example, the sequence of steps following the term "obtained", even though such a restrictive understanding is always included as a preferred embodiment in the term "obtained" or "defined".

[0052] Advantageous embodiments of the catalyst system of the invention, corresponding methods for producing the catalyst system and uses of the catalyst system are defined below and in the corresponding dependent claims.

[0053] In one embodiment according to the present invention, the at least one water-insoluble calcium salt is selected from octacalcium phosphate, hydroxyapatite, chloroapatite, fluoroapatite, carbonapatite and mixtures thereof, preferably the at least one water-insoluble calcium salt is hydroxyapatite.

[0054] In another embodiment, the ratio of at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite (preferably to calcite) is in the range of 1:9 to 9:1 by weight, preferably 1:7 to 8:1, more preferably 1:5 to 7:1, even more preferably 1:4 to 7:1.

[0055] According to another embodiment, the transition metal compound is selected from the group consisting of palladium compounds, platinum compounds, copper compounds and mixtures thereof.

[0056] According to another embodiment of the catalyst system of the present invention, the transition metal compound is selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4, copper, Cu2O, Cu2S, copper(I)-thiophene-2-carboxylate, CuBr, CuCN, CuCl, CuF, CuI, CuH, CuSCN, CuBr2, Cu CO3, CuCl2, CuF2, Cu(NO3)2, Cu3(PO4)2, CuO, CuO2, Cu(OH)2, CuI2, CuS, CuSO4, Cu2(OAc)4 and mixtures thereof, preferably the transition metal compound is selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe) PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, elemental platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4 and mixtures thereof.

[0057] According to yet another embodiment, the surface-reacted calcium carbonate has:

[0058] (i) Measured at 27 m using nitrogen and the BET method according to ISO 9277:2010 2 / g to 180m 2 / g, preferably 25m 2 / g to 160m 2 / g, more preferably 30m 2 / g to 150m 2 Specific surface area in the range of / g;

[0059] (ii) a d in the range of 1 μm to 75 μm, preferably 2 μm to 50 μm, more preferably 3 μm to 40 μm, even more preferably 4 μm to 30 μm, most preferably 5 μm to 15 μm50 (volume);

[0060] (iii) a d in the range of 2 μm to 150 μm, preferably 4 μm to 100 μm, more preferably 6 μm to 80 μm, even more preferably 8 μm to 60 μm, most preferably 10 μm to 30 μm 98 (volume); and / or

[0061] (iv) The pore size at 0.2 cm calculated from mercury porosimetry measurements 3 / g to 2.0cm 3 / g, preferably 0.4cm 3 / g to 1.8cm 3 / g, most preferably 0.6cm 3 / g to 1.6cm 3 / g range of intrusion specific pore volume within the particles.

[0062] In yet another embodiment, the catalyst of the present invention further comprises one or more reaction products obtained by the reaction of a transition metal compound with the surface-reacted calcium carbonate.

[0063] According to yet another embodiment, the content of the transition metal compound and / or one or more reaction products thereof is in the range of 0.1 wt.-% to 60 wt.-%, preferably 0.1 wt.-% to 30 wt.-%, more preferably 0.1 wt.-% to 20 wt.-%, even more preferably 0.1 wt.-% to 10 wt.-%, most preferably 0.2 wt.-% to 5 wt.-%, based on the weight of the transition metal compound / total weight of the catalyst system.

[0064] In one embodiment of the method according to the invention, the method is characterized in that:

[0065] (i) the at least one surface-reacted calcium carbonate of step (a) is provided in the form of a suspension in a liquid medium; and / or

[0066] (ii) The at least one transition metal compound of step (b) is provided in the form of a solution or suspension in a liquid medium, preferably in the form of a solution.

[0067] In another embodiment, the method comprising steps (a) to (c) further comprises the step (d): removing at least part of the liquid medium contained in the mixture of step (c) by evaporation and / or filtration to obtain a concentrated mixture.

[0068] According to another embodiment, the method of the present invention further comprises the step (e): heat treating the mixture of step (c) or the concentrated mixture of step (d) at a temperature below 400°C, preferably at a temperature in the range of 170°C to 400°C, more preferably in the range of 200°C to 300°C, even more preferably in the range of 250°C to 310°C, and most preferably in the range of 280°C to 320°C.

[0069] According to yet another embodiment of the process according to the present invention, the transition metal compound is selected from the group consisting of palladium compounds, platinum compounds, copper compounds and mixtures thereof.

[0070] In another embodiment of the method according to the present invention, the transition metal compound is selected from the group consisting of elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd d(dba)2, Pd(H2NCH2CH2NH2)Cl2, platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4, copper, Cu2O, Cu2S, copper(I)-thiophene-2-carboxylate, CuBr, CuCN, CuCl, CuF, CuI, CuH, CuSCN, CuBr2, CuC O3, CuCl2, CuF2, Cu(NO3)2, Cu3(PO4)2, CuO, CuO2, Cu(OH)2, CuI2, CuS, CuSO4, Cu2(OAc)4 and mixtures thereof, preferably the transition metal compound is selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)Pd dCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, elemental platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4 and mixtures thereof.

[0071] In another embodiment of the method of the present invention, the liquid medium is a non-polar solvent, a polar solvent or a mixture thereof, preferably a non-polar solvent is selected from pentane, cyclopentane, hexane, cyclohexane, benzene, toluene, 1,4-dihydrogen peroxide, The invention relates to a polar solvent selected from the group consisting of tetrahydrofuran, ethyl acetate, acetone, dimethylformamide, acetonitrile, dimethyl sulfoxide, nitromethane, propylene carbonate, formic acid, n-butanol, isopropanol, n-propanol, ethanol, methanol, acetic acid, water and mixtures thereof.

[0072] In yet another embodiment, the transition metal compound is Na2PdCl4 and / or Na2PtCl4, and the liquid medium is a polar solvent, preferably water; and / or the transition metal compound is Pd(acac)2 and / or Pt(acac)2, and the liquid medium is a non-polar solvent, preferably toluene.

[0073] According to another embodiment, the catalyst system of the present invention is used in a catalytic process comprising steps (a) to (c), wherein the process further comprises step (d): recovery and recycling of the catalyst system.

[0074] According to another embodiment, the catalyst system of the invention is used in a catalytic process comprising a chemical reaction selected from one or more of the following reaction types: hydrogenolysis, CC coupling and CC cross-coupling, CN cross-coupling, CO cross-coupling, CS cross-coupling, cycloaddition reactions, olefin hydrogenation and alkyne hydrogenation, allylic substitution, reduction of nitro groups and hydroformylation of aryl halides, preferably hydrogenolysis, CC coupling and CC cross-coupling.

[0075] As described above, the method for providing the catalyst system of the present invention comprises steps (a) to (c). The method optionally further comprises steps (d) and (e). It should be understood that the method of the present invention can be carried out as a continuous process or a batch process. Preferably, the method of the present invention is carried out as a continuous process.

[0076] In the following, reference is made to further details of the present invention, in particular to the aforementioned steps of the process of the present invention for the surface treatment of the surface-reacted calcium carbonate.

[0077] Step (a): Providing at least one surface-reacted calcium carbonate

[0078] According to step (a) of the process of the present invention, surface-reacted calcium carbonate is provided.Surface-reacted calcium carbonate is also called functionalized calcium carbonate (FCC).

[0079] It should be understood that the surface-reacted calcium carbonate may be one or more surface-reacted calcium carbonates.

[0080] In one embodiment of the invention, the surface-reacted calcium carbonate comprises a surface-reacted calcium carbonate, preferably consisting of a surface-reacted calcium carbonate. Alternatively, the surface-reacted calcium carbonate comprises two or more surface-reacted calcium carbonates, preferably consisting of two or more surface-reacted calcium carbonates. For example, the surface-reacted calcium carbonate comprises two or three surface-reacted calcium carbonates, preferably consisting of two or three surface-reacted calcium carbonates.

[0081] Preferably, the surface-reacted calcium carbonate comprises, more preferably consists of, a surface-reacted calcium carbonate.

[0082] The surface-reacted calcium carbonate is formed by reacting CO2 with one or more H3O + The reaction product of ion donor treated ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) wherein CO2 is reacted with H3O + The ion donor is formed in situ and / or supplied from an external source. + Reaction of the ion donor, the surface-reacted calcium carbonate comprises GNCC or PCC and at least one water-insoluble calcium salt.

[0083] In a preferred embodiment, the surface-reacted calcium carbonate comprises GNCC or PCC and at least one water-insoluble calcium salt present on at least a portion of the surface of the GNCC or PCC.

[0084] In the context of the present invention, H3O + The ion donor is a Bronsted acid and / or an acid salt.

[0085] In a preferred embodiment of the invention, the surface-reacted calcium carbonate is obtained by a method comprising the following steps:

[0086] (a) providing a suspension of ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC);

[0087] (b) adding a precipitate having a pK at 20° C. to the suspension provided in step (a) a A value of 0 or less or a pK value of 0 or less at 20°C a at least one acid with a value of 0 to 2.5; and

[0088] (c) treating the suspension provided in step (a) with CO2 before, during or after step (b).

[0089] According to another embodiment, the surface-reacted calcium carbonate is obtained by a process comprising the steps of:

[0090] (a) providing ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC);

[0091] (b) providing at least one water-soluble acid;

[0092] (c) providing gaseous CO2; and

[0093] (d) contacting the GNCC or PCC provided in step (a), the at least one acid provided in step (b), and the gaseous CO2 provided in step (c);

[0094] It is characterized in that: (i) the at least one acid provided in step (b) has a pK value at 20°C related to the ionization of its first available hydrogen a greater than 2.5 and less than or equal to 7, and upon loss of the first available hydrogen forms a corresponding anion capable of forming a water-soluble calcium salt; and (ii) after contacting the at least one water-soluble acid provided in step (b) with the GNCC or PCC provided in step (a), additionally providing at least one water-soluble salt, wherein the water-soluble salt has a pK associated with the ionization of the first available hydrogen at 20° C. in the case of a hydrogen-containing salt. a is greater than 7, and the salt anion of the water-soluble salt is capable of forming a water-insoluble calcium salt.

[0095] The source of calcium carbonate (e.g., "ground natural calcium carbonate" (GNCC)) is preferably selected from calcium carbonate-containing minerals selected from the group consisting of marble, chalk, limestone, and mixtures thereof. Natural calcium carbonate may contain other naturally occurring components, such as magnesium carbonate, aluminosilicates, etc. According to one embodiment, natural calcium carbonate (e.g., GNCC) comprises calcium carbonate in the mineralogical crystal form of aragonite, vaterite, or calcite, or mixtures thereof.

[0096] Typically, the grinding of ground natural calcium carbonate can be carried out in a dry grinding process or a wet grinding process, and can be carried out with any conventional grinding device, for example, under conditions such that the crushing is mainly caused by the impact of the second object, that is, in one or more of the following: ball mill, rod mill, vibrating mill, roller crusher, centrifugal impact mill, vertical bead mill, grinder, pin mill, hammer mill, pulverizer, shredder, deblocker (declumper), knife cutter or other such equipment known to the technician. In the case where the ground natural calcium carbonate comprises wet-ground calcium carbonate, the grinding step can be carried out under conditions such that autogenous grinding occurs and / or by horizontal ball milling and / or other such methods known to the technician. The wet-treated ground natural calcium carbonate thus obtained can be washed and dehydrated by known methods (for example, by flocculation, filtration or forced evaporation) before drying. The subsequent drying step (if necessary) can be carried out in a single step (for example, spray drying), or in at least two steps. It is also common to make such mineral materials undergo a beneficiation step (for example, flotation, bleaching or magnetic separation step) to remove impurities.

[0097] In the meaning of the present invention, "precipitated calcium carbonate" (PCC) is a synthetic material, which is usually precipitated after reacting CO2 and calcium hydroxide in an aqueous environment or obtained by precipitation from a solution of calcium ions and carbonate ions (e.g., CaCl2 and Na2CO3). Another possible way to produce PCC is the lime soda process, or the Solvay process (wherein PCC is a by-product of synthetic ammonia). Precipitated calcium carbonate exists in three main crystalline forms: calcite, aragonite and vaterite, and each of these crystalline forms has many different polymorphs (crystal habits). Calcite has a trigonal structure, and its typical crystal habits are, for example, scalenohedron (S-PCC), rhombohedron (R-PCC), hexagonal prism, axonopter, colloidal (C-PCC), cubic and prismatic (P-PCC). Aragonite has an orthorhombic structure, and its typical crystal habit is twinned hexagonal prism crystals, as well as various types of slender prisms, curved blades, steep pyramids, chisel-shaped crystals, branched trees, and coral or worm-like forms. Hexagonal calcium carbonate belongs to the hexagonal crystal system. The obtained aqueous PCC slurry can be mechanically dehydrated and dried.

[0098] According to one embodiment of the present invention, the precipitated calcium carbonate comprises calcium carbonate in the mineral crystal form of aragonite, vaterite or calcite, or a mixture thereof.

[0099] Calcium carbonate can be precipitated by using CO2 and at least one H3O + The ion donor treatment is preceded by grinding in the same manner as described above for grinding natural calcium carbonate.

[0100] According to one embodiment of the present invention, the natural calcium carbonate or precipitated calcium carbonate has a weight median particle size d 50 According to another embodiment of the present invention, the natural calcium carbonate or precipitated calcium carbonate is in the form of particles with a top cut particle size d 98 The invention is in the form of particles with a weight range of 0.15 μm to 55 μm, preferably 1 μm to 40 μm, more preferably 2 μm to 25 μm, most preferably 3 μm to 15 μm, especially 4 μm.

[0101] The natural calcium carbonate or precipitated calcium carbonate can be used dry or suspended in water. Preferably, the content of natural calcium carbonate or precipitated calcium carbonate of the corresponding aqueous slurry is in the range of 1 wt % to 90 wt %, more preferably 3 wt % to 60 wt %, even more preferably 5 wt % to 40 wt %, most preferably 10 wt % to 25 wt %, based on the total weight of the slurry.

[0102] One or more H3O for preparing surface-reacted calcium carbonate + The ion donor may be H3O generated under preparation conditions. + ions, or any strong, medium or weak acid or mixtures thereof. According to the present invention, at least one H3O + The ion donor can also be H3O generated under the preparation conditions. + Acid salts of ions.

[0103] According to one embodiment, at least one H3O + The ion donor has a pK at 20°C. a A strong acid of 0 or less.

[0104] According to another embodiment, at least one H3O + The ion donor has a pK at 20°C. a A medium-strong acid with a pK value between 0 and 2.5. a is 0 or less, the acid is preferably selected from sulfuric acid, hydrochloric acid or a mixture thereof. a 0 to 2.5, then H3O + The ion donor is preferably selected from H2SO3, H3PO4, oxalic acid or a mixture thereof. + The ion donor may also be an acid salt, for example, a salt of a corresponding cation such as Li + 、Na + or K + At least partially neutralized HSO4 - or H2PO4 -; or by corresponding cations such as Li + 、Na + , K + Mg 2+ or Ca 2+ At least partially neutralized HPO4 2- . At least one H3O + The ion donor may also be a mixture of one or more acids and one or more acid salts.

[0105] According to another embodiment, at least one H3O + An ion donor is a weak acid whose pK associated with the ionization of the first available hydrogen when measured at 20°C is a A value greater than 2.5 and less than or equal to 7, and having a corresponding anion capable of forming a water-soluble calcium salt. Subsequently, at least one water-soluble salt is additionally provided, the water-soluble salt having a pK associated with the ionization of the first available hydrogen when measured at 20° C. in the case of a hydrogen-containing salt. a is greater than 7, and its salt anion is capable of forming a water-insoluble calcium salt. According to a more preferred embodiment, the pK of the weak acid at 20°C is a The value is greater than 2.5 to 5, and more preferably, the weak acid is selected from acetic acid, formic acid, propionic acid and mixtures thereof. Exemplary cations of the water-soluble salt are selected from potassium, sodium, lithium and mixtures thereof. In a more preferred embodiment, the cation is sodium or potassium. Exemplary anions of the water-soluble salt are selected from phosphate, dihydrogen phosphate, monohydrogen phosphate, oxalate, silicate, mixtures thereof and hydrates thereof. In a more preferred embodiment, the anion is selected from phosphate, dihydrogen phosphate, monohydrogen phosphate, mixtures thereof and hydrates thereof. In a most preferred embodiment, the anion is selected from dihydrogen phosphate, monohydrogen phosphate, mixtures thereof and hydrates thereof. The addition of the water-soluble salt can be carried out dropwise or in one step. In the case of dropwise addition, the addition is preferably carried out over a period of 10 minutes. More preferably, the salt is added in one step.

[0106] According to one embodiment of the present invention, at least one H3O + The ion donor is selected from hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, citric acid, oxalic acid, acetic acid, formic acid and mixtures thereof. Preferably, at least one H3O + The ion donor is selected from hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, oxalic acid, the corresponding cation such as Li + 、Na + or K + At least partially neutralized H2PO4 - , by corresponding cations such as Li + 、Na + , K + Mg 2+or Ca 2+ At least partially neutralized HPO4 2- , and mixtures thereof; more preferably, at least one acid is selected from hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, oxalic acid or mixtures thereof. Particularly preferably, H3O + The ion donor is phosphoric acid.

[0107] One or more H3O + The ion donor is added to the suspension as a concentrated solution or a more dilute solution. Preferably, H3O + The molar ratio of ion donor to natural calcium carbonate or precipitated calcium carbonate is from 0.01 to 4, more preferably from 0.02 to 2, even more preferably from 0.05 to 1, and most preferably from 0.1 to 0.58.

[0108] In another preferred embodiment, at least one H3O + The ion donor is selected from hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, citric acid, oxalic acid, acetic acid, formic acid and mixtures thereof, wherein H3O + The molar ratio of ion donor to natural calcium carbonate or precipitated calcium carbonate is from 0.01 to 4, more preferably from 0.02 to 2, even more preferably from 0.05 to 1, and most preferably from 0.1 to 0.58.

[0109] In a particularly preferred embodiment, at least one H3O + The ion donor is a mixture of phosphoric acid and citric acid; more preferably, H3O + The molar ratio of ion donor to natural calcium carbonate or precipitated calcium carbonate is from 0.01 to 4, more preferably from 0.02 to 2, even more preferably from 0.05 to 1, and most preferably from 0.1 to 0.58.

[0110] As described above, at least one H3O + Treatment of GNCC or PCC with an ion donor and CO2 can result in the formation of at least one water-insoluble calcium salt. Thus, the surface-reacted calcium carbonate comprises GNCC or PCC and at least one water-insoluble calcium salt other than calcium carbonate. In one embodiment, the at least one water-insoluble calcium salt is present on at least a portion of the surface of the GNCC or PCC.

[0111] Use phosphoric acid, H2PO4 - or HPO4 2- As H3O + The ion donor may result in the formation of hydroxyapatite. Thus, in a preferred embodiment, the at least one water-insoluble calcium salt is hydroxyapatite.

[0112] The amount of at least one water-insoluble calcium salt present in the surface-reacted calcium carbonate relative to the amount of calcite, aragonite and / or vaterite present in the GNCC or PCC can be quantified by XRD using the Rietveld method.

[0113] In a more preferred embodiment, the at least one water-insoluble calcium salt is hydroxyapatite, wherein the surface-reacted calcium carbonate provides a ratio of hydroxyapatite to calcite, aragonite and / or vaterite (preferably with calcite) by weight in the range of 1:99 to 99: 1. More preferably, the surface-reacted calcium carbonate provides a ratio of hydroxyapatite to calcite, aragonite and / or vaterite (preferably with calcite) by weight in the range of 1:9 to 9: 1, preferably 1:7 to 8: 1, more preferably 1:5 to 7: 1, most preferably 1:4 to 7: 1.

[0114] In a similar manner, use other H3O + The ion donor may result in the formation of a corresponding water-insoluble calcium salt other than calcium carbonate on at least part of the surface of the surface-reacted calcium carbonate. In one embodiment, the at least one water-insoluble calcium salt is therefore selected from octacalcium phosphate, hydroxyapatite, chlorapatite, fluoroapatite, carbonapatite and mixtures thereof, wherein the surface-reacted calcium carbonate exhibits a ratio of at least one water-insoluble calcium salt relative to calcite, aragonite and / or vaterite (preferably with calcite) in the range of 1:99 to 99:1, preferably 1:9 to 9:1, more preferably 1:7 to 8:1, even more preferably 1:5 to 7:1, most preferably 1:4 to 7:1 by weight.

[0115] As an alternative, H3O can also be added before suspending the natural calcium carbonate or precipitated calcium carbonate. + An ion donor is added to the water.

[0116] In the next step, the natural calcium carbonate or precipitated calcium carbonate is treated with CO2. If a strong acid such as sulfuric acid or hydrochloric acid is used for the H3O + Alternatively or additionally, CO2 may be supplied by an external source.

[0117] H3O + The ion donor treatment and the CO2 treatment can be carried out simultaneously, which is the case when using strong or medium-strong acids. It is also possible to first use, for example, a solution with a pK at 20°C. a Medium to strong acid in the range of 0 to 2.5 H3O + Ion donor treatment, where CO2 is formed in situ, therefore, the CO2 treatment will automatically react with H3O + Ion donor treatment was performed simultaneously, followed by additional treatment with CO2 supplied from an external source.

[0118] Preferably, the concentration of gaseous CO2 in the suspension is such by volume that the ratio (volume of suspension):(volume of gaseous CO2) is from 1:0.05 to 1:20, even more preferably from 1:0.05 to 1:5.

[0119] In a preferred embodiment, H3O + The ion donor treatment step and / or the CO2 treatment step are repeated at least once, more preferably several times. According to one embodiment, at least one H3O + The ion donor is added over a period of at least about 5 minutes, preferably at least about 10 minutes, typically about 10 minutes to about 20 minutes, more preferably about 30 minutes, even more preferably about 45 minutes, and sometimes about 1 hour or longer.

[0120] In H3O + After the ion donor treatment and the CO2 treatment, the pH of the aqueous suspension measured at 20°C naturally reaches a value greater than 6.0, preferably greater than 6.5, more preferably greater than 7.0, even more preferably greater than 7.5, thereby preparing a surface-reacted natural calcium carbonate or precipitated calcium carbonate as an aqueous suspension with a pH greater than 6.0, preferably greater than 6.5, more preferably greater than 7.0, even more preferably greater than 7.5.

[0121] Further details on the preparation of surface-reacted natural calcium carbonate are disclosed in WO 00 / 39222 A1, WO 2004 / 083316 A1, WO 2005 / 121257 A2, WO 2009 / 074492 A1, EP 2 264 108 A1, EP 2 264109 A1 and US 2004 / 0020410 A1, the contents of these references are included in the present application.

[0122] Similarly, surface-reacted precipitated calcium carbonate can be obtained. As can be known in detail from WO 2009 / 074492 A1, surface-reacted precipitated calcium carbonate is obtained by reacting the precipitated calcium carbonate with H3O + The invention relates to a method for obtaining a slurry of surface-reacted precipitated calcium carbonate by contacting an anion dissolved in an aqueous medium and capable of forming a water-insoluble calcium salt in an aqueous medium to form a slurry of surface-reacted precipitated calcium carbonate, wherein the surface-reacted precipitated calcium carbonate comprises an at least partially crystallized insoluble calcium salt of the anion formed on the surface of at least part of the precipitated calcium carbonate.

[0123] The dissolved calcium ions correspond to the amount of H3O in the precipitated calcium carbonate. + ions and the dissolved calcium ions are excessive when the naturally occurring dissolved calcium ions are dissolved, wherein the H3O +The ion is provided only in the form of a counterion to the anion (ie, by addition of an acid or non-calcium acid salt form of the anion) and in the absence of any other calcium ions or sources of calcium ion generation.

[0124] The excess dissolved calcium ions are preferably provided by the addition of a soluble neutral or acidic calcium salt, or by the addition of an acid or a neutral or acidic non-calcium salt which generates a soluble neutral or acidic calcium salt in situ.

[0125] The H3O + The ions may be provided by the addition of an acid or acid salt of the anion, or by the addition of an acid or acid salt which simultaneously provides all or a portion of the excess dissolved calcium ions.

[0126] In another preferred embodiment of the preparation of surface-reacted natural calcium carbonate or precipitated calcium carbonate, natural calcium carbonate or precipitated calcium carbonate is reacted with acid and / or CO in the presence of at least one compound selected from the group consisting of silicates, silicon dioxide, aluminum hydroxide, alkaline earth metal aluminates (e.g. sodium aluminate or potassium aluminate), magnesium oxide, aluminum sulfate or mixtures thereof. Preferably, at least one silicate is selected from aluminum silicate, calcium silicate or alkaline earth metal silicate.

[0127] In another preferred embodiment, the at least one compound is aluminum sulfate hexadecahydrate. In a particularly preferred embodiment, the at least one compound is aluminum sulfate hexadecahydrate, wherein at least one H3O + The ion donor is selected from hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, citric acid, oxalic acid, acetic acid, formic acid and mixtures thereof; more preferably, the H3O + The molar ratio of ion donor to natural calcium carbonate or precipitated calcium carbonate is from 0.01 to 4, more preferably from 0.02 to 2, even more preferably from 0.05 to 1, and most preferably from 0.1 to 0.58.

[0128] The aforementioned components may be added to the aqueous suspension comprising natural calcium carbonate or precipitated calcium carbonate prior to the addition of the acid and / or CO2.

[0129] Alternatively, the aforementioned components can be added to an aqueous suspension of natural calcium carbonate or precipitated calcium carbonate when the reaction of natural calcium carbonate or precipitated calcium carbonate with acid and CO2 has already begun. More details on the preparation of surface-reacted natural calcium carbonate or precipitated calcium carbonate in the presence of at least one silicate and / or silicon dioxide and / or aluminum hydroxide and / or alkaline earth metal aluminate component are disclosed in WO2004 / 083316A1, the content of which is hereby included in the present application.

[0130] The surface-reacted calcium carbonate may be kept in suspension, optionally further stabilized by a dispersant. Conventional dispersants known to the skilled person may be used. Preferred dispersants include polyacrylic acid and / or carboxymethyl cellulose.

[0131] Alternatively, the aqueous suspension may be dried to obtain a solid (ie dry or containing as little water as possible and not in a fluid form) surface-reacted natural calcium carbonate or precipitated calcium carbonate in the form of granules or powder.

[0132] The surface-reacted calcium carbonate can have different particle shapes, for example, the shape of a rose, a golf ball, and / or a brain.

[0133] In a preferred embodiment, the specific surface area of ​​the surface-reacted calcium carbonate is 15 m 2 / g to 200m 2 / g, preferably 27m 2 / g to 180m 2 / g, more preferably 25m 2 / g to 160m 2 / g, even more preferably 30m 2 / g to 150m 2 / g, most preferably 48m 2 / g to 140m 2 In another embodiment, the specific surface area of ​​the surface-reacted calcium carbonate is 120 m2, measured according to ISO 9277:2010 using nitrogen and the BET method. 2 / g or less, more preferably 60m 2 / g to 120m 2 / g, most preferably 70m 2 / g to 105m 2 For example, the specific surface area of ​​surface-reacted calcium carbonate measured using nitrogen and the BET method according to ISO 9277:2010 may be 75 m 2 / g to 100m 2 / g.

[0134] It may further be preferred that the volume median particle size d of the surface-reacted calcium carbonate particles is 50 The volume median particle size d of the surface-reacted calcium carbonate particles is 1 μm to 75 μm, preferably 2 μm to 50 μm, more preferably 3 μm to 40 μm, even more preferably 4 μm to 30 μm, most preferably 5 μm to 15 μm. According to another preferred embodiment, the volume median particle size d of the surface-reacted calcium carbonate particles is 1 μm to 75 μm, preferably 2 μm to 50 μm, more preferably 3 μm to 40 μm, even more preferably 4 μm to 30 μm, most preferably 5 μm to 15 μm. 50 (volume) is 1.5 μm to 12 μm, preferably 2 μm to 5 μm or 6 μm to 10 μm.

[0135] It may further be preferred that the particle size d of the surface-reacted calcium carbonate particles is 98 The volume median particle size d of the surface-reacted calcium carbonate particles is 2 μm to 150 μm, preferably 4 μm to 100 μm, more preferably 6 μm to 80 μm, even more preferably 8 μm to 60 μm, and most preferably 10 μm to 30 μm. 98 (volume) is 5 μm to 20 μm, preferably 8 μm to 12 μm or 13 μm to 18 μm.

[0136] According to another embodiment, the surface-reacted calcium carbonate has an intra-particle intrusion specific pore volume of 0.1 cm 3 / g to 2.3cm 3 / g, more preferably 0.2cm 3 / g to 2.0cm 3 / g, particularly preferably 0.25cm 3 / g to 1.8cm 3 / g, most preferably 0.3cm 3 / g to 1.6cm 3 / g range.

[0137] The particle internal pore size of the surface-reacted calcium carbonate, as determined by mercury porosimetry, is preferably in the range of 0.004 μm to 1.6 μm, more preferably in the range of 0.005 μm to 1.3 μm, particularly preferably in the range of 0.006 μm to 1.15 μm, most preferably in the range of 0.007 μm to 1.0 μm, for example in the range of 0.004 μm to 0.50 μm.

[0138] As described above, specific pore volume can be measured using mercury intrusion porosimetry measurements using a Micromeritics Autopore V 9620 mercury porosimeter.

[0139] For the purpose of step (a) of the present invention, the surface-reacted calcium carbonate can be provided in dry form or as a suspension in a suitable liquid medium. Unless otherwise specified, the term "dried" or "drying" refers to a material having a constant weight at 150° C., wherein constant weight means that the weight change is 1 mg or less per 5 g sample in 30 seconds.

[0140] In a preferred embodiment, the surface-reacted calcium carbonate is provided in the form of a suspension in a liquid medium.

[0141] In the case where the surface-reacted calcium carbonate is provided as suspension or slurry in step (a), suspension or slurry comprise suitable liquid medium. The liquid medium may be different from the liquid medium described below as a suitable liquid medium for providing at least one transition metal compound of solution or suspension form. However, in a preferred embodiment, the liquid medium for providing at least one surface-reacted calcium carbonate is identical with the liquid medium for providing at least one transition metal compound.

[0142] Typically, the liquid medium can be a non-polar solvent, a polar solvent or a mixture thereof, preferably a non-polar solvent selected from pentane, cyclopentane, hexane, cyclohexane, benzene, toluene, 1,4-dihydrogen peroxide, Preferably, the liquid medium is selected from water, ethanol, ethanol / water mixture and toluene.

[0143] The solid content of the slurry may be in the range of 1 wt % to 90 wt %, preferably 3 wt % to 60 wt %, more preferably 5 wt % to 40 wt %, most preferably 10 wt % to 25 wt %, based on the total weight of the slurry.

[0144] Step (b): Providing at least one transition metal compound

[0145] In step (b) of the production method according to the invention, at least one transition metal compound is provided.

[0146] A "transition metal" within the meaning of the present invention is any element in the d-block of the periodic table.

[0147] Preferably, the transition metal exhibits catalytic activity in chemical reactions. Thus, the transition metal may be selected from the following metals: titanium, chromium, manganese, iron, cobalt, copper, zinc, zirconium, molybdenum, ruthenium, palladium, silver, osmium, platinum, gold, mercury and mixtures thereof.

[0148] According to another preferred embodiment of the present invention, the transition metal is selected from copper, palladium, platinum and mixtures thereof, preferably palladium and platinum. In a particularly preferred embodiment, the transition metal is palladium.

[0149] In the meaning of the present invention, the term "compound" shall include all kinds of compounds associated by chemical bonds, including elemental forms, ie elemental transition metals associated by metallic bonds.

[0150] In principle, there are four types of compounds, depending on how the constituent atoms are held together: molecules held together by covalent bonds, salts held together by ionic bonds, intermetallic compounds held together by metallic bonds, and certain complexes held together by coordinate covalent bonds. Thus, a transition metal compound can be a molecular transition metal compound, a transition metal salt, a metallic transition metal compound containing an elemental transition metal, or a transition metal complex.

[0151] According to a preferred embodiment of the present invention, the transition metal compound is a transition metal salt or a transition metal complex.

[0152] In another preferred embodiment according to the present invention, the transition metal salt comprises one or more of the following counterions: hydride, oxide, hydroxide, sulfide, fluoride, chloride, bromide, iodide, carbonate, acetate, cyanide, thiocyanate, nitrate, phosphate and sulfate.

[0153] In another preferred embodiment, the transition metal complex comprises one or more of the following ligands: acetylacetonate (acac), chloride, acetate, triphenylphosphine, 1,1'-bis(diphenylphosphino)ferrocene (dppf), 1,2-bis(diphenylphosphino)ethane (dppe), 1,3-bis(diphenylphosphino)propane (dppp), 1,4-bis(diphenylphosphino)butane (dppb), allyl, dibenzylideneacetone or dibenzaldehyde (dba) and ethylenediamine.

[0154] Thus, according to another embodiment, the transition metal is an element in the d-block of the periodic table, preferably selected from titanium, chromium, manganese, iron, cobalt, copper, zinc, zirconium, molybdenum, ruthenium, palladium, silver, osmium, platinum, gold, mercury and mixtures thereof, and the transition metal compound is a molecular transition metal compound, a transition metal salt, a metallic transition metal compound comprising an elemental transition metal, or a transition metal complex.

[0155] In a preferred embodiment, the transition metal is selected from titanium, chromium, manganese, iron, cobalt, copper, zinc, zirconium, molybdenum, ruthenium, palladium, silver, osmium, platinum, gold, mercury and mixtures thereof, preferably copper, palladium, platinum and mixtures thereof, more preferably palladium, platinum and mixtures thereof, and most preferably palladium; the transition metal compound is a transition metal salt or a transition metal complex. In another preferred embodiment, the aforementioned transition metal salt comprises one or more of the following counterions: hydride, oxide, hydroxide, sulfide, fluoride, chloride, bromide, iodide, carbonate, acetate, cyanide, thiocyanate, nitrate, phosphate and sulfate, and / or the aforementioned transition metal complex comprises one or more of the following ligands: acac, chloride, acetate, triphenylphosphine, dppf, dppe, dppp, dppb, allyl, dba and ethylenediamine.

[0156] According to another embodiment, the transition metal compound is selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba) 2. Pd(H2NCH2CH2NH2)Cl2, platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4, copper, Cu2O, Cu2S, copper(I)-thiophene-2-carboxylate, CuBr, CuCN, CuCl, CuF, CuI, CuH, CuSCN, CuBr2, CuCO3, C uCl2, CuF2, Cu(NO3)2, Cu3(PO4)2, CuO, CuO2, Cu(OH)2, CuI2, CuS, CuSO4, Cu2(OAc)4 and mixtures thereof, preferably the transition metal compound is selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdC l2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, elemental platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4 and mixtures thereof.

[0157] According to another embodiment of the present invention, the transition metal compound is selected from Pd(acac)2, Pt(acac)2, Na2PdCl4, Na2PtCl4 and mixtures thereof, preferably Pd(acac)2, Pt(acac)2, more preferably, the transition metal compound is Pd(acac)2.

[0158] For the purposes of step (b), the transition metal compound can in principle be provided in any form, which means that the transition metal compound can be provided as a pure compound or it can be provided in the form of a solution or suspension in a liquid medium.

[0159] Providing in a liquid medium may be preferred, as this may result in a more homogeneous mixture in any subsequent step, for example in the contacting step (c) of the process of the invention for making a catalyst system. For the same reason, solutions may be preferred over suspensions. In a preferred embodiment, the transition metal compound in step (b) is therefore provided in the form of a solution or suspension in a liquid medium, preferably in the form of a solution.

[0160] Typically, protic solvents and aprotic solvents or polar solvents and nonpolar solvents can be used. Thus, non-limiting examples of suitable liquid media include water, ethanol and C 3-5 Alkyl alcohols, acetone, tetrahydrofuran, acetonitrile, dimethyl sulfoxide, dimethylformamide, chloroform, dichloromethane, ethyl acetate, diethyl ether, methyl tert-butyl ether, benzene, toluene and mixtures thereof. The skilled person will know how to select suitable solvents and mixtures thereof.

[0161] In a preferred embodiment, the transition metal compound is therefore selected from palladium compounds, platinum compounds, copper compounds and mixtures thereof, preferably the transition metal compound is a transition metal salt or a transition metal complex, more preferably the transition metal compound is Pd(acac)2 and / or Pt(acac)2, wherein the transition metal compound in step (b) is provided in the form of a solution or suspension in a liquid medium, preferably in the form of a solution.

[0162] According to another embodiment, the liquid medium is a non-polar solvent, a polar solvent or a mixture thereof, preferably the non-polar solvent is selected from pentane, cyclopentane, hexane, cyclohexane, benzene, toluene, 1,4-dimethoxybenzene, The invention relates to a polar solvent selected from the group consisting of tetrahydrofuran, ethyl acetate, acetone, dimethylformamide, acetonitrile, dimethyl sulfoxide, nitromethane, propylene carbonate, formic acid, n-butanol, isopropanol, n-propanol, ethanol, methanol, acetic acid, water and mixtures thereof.

[0163] According to yet another embodiment of the present invention, the liquid medium is selected from the group consisting of water, ethanol, ethanol / water mixtures and toluene.

[0164] According to another embodiment, the transition metal is selected from titanium, chromium, manganese, iron, cobalt, copper, zinc, zirconium, molybdenum, ruthenium, palladium, silver, osmium, platinum, gold, mercury and mixtures thereof, wherein the metal compound is a transition metal salt or a transition metal complex, and wherein the transition metal compound is provided in the form of a solution or suspension in a liquid medium (preferably in the form of a solution). In another preferred embodiment, the aforementioned transition metal salt comprises one or more of the following counterions: hydride, oxide, hydroxide, sulfide, fluoride, chloride, bromide, iodide, carbonate, acetate, cyanide, thiocyanate, nitrate, phosphate and sulfate, and / or the aforementioned transition metal complex comprises one or more of the following ligands: acac, chloride, acetate, triphenylphosphine, dppf, dppe, dppp, dppb, allyl, dba and ethylenediamine.

[0165] According to another embodiment, the transition metal compound is selected from palladium compounds, platinum compounds, copper compounds and mixtures thereof; preferably, the transition metal compound is a transition metal salt or a transition metal complex; more preferably, the transition metal compound is selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, di(acetic acid) ester) triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, elemental platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4, elemental copper, Cu2O, Cu2S, copper(I)-thiophene-2-carboxylate, CuBr, CuCN, CuCl, CuF, CuI, CuH, CuSCN, CuBr2, CuCO3, CuCl2, CuF2, Cu(NO3)2, C u3(PO4)2, CuO, CuO2, Cu(OH)2, CuI2, CuS, CuSO4, Cu2(OAc)4 and mixtures thereof, preferably the transition metal compound is selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II ), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, elemental platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4 and mixtures thereof, wherein the transition metal compound is provided in the form of a solution or suspension in a liquid medium (preferably in the form of a solution), wherein the liquid medium is an organic solvent, preferably toluene; or the liquid medium is an aqueous solvent, preferably water; or the liquid medium is a mixture of an organic solvent and water, preferably a mixture of ethanol and water.

[0166] According to a preferred embodiment, the transition metal compound is selected from palladium compounds, platinum compounds, copper compounds and mixtures thereof, preferably the transition metal compound is a transition metal salt or a transition metal complex, more preferably the transition metal compound is Pd(acac)2 and / or Pt(acac)2, wherein the liquid medium is an organic solvent, preferably benzene or toluene, more preferably toluene.

[0167] According to another preferred embodiment, the transition metal compound is selected from palladium compounds, platinum compounds, copper compounds and mixtures thereof, preferably the transition metal compound is a transition metal salt or a transition metal complex, more preferably the transition metal compound is Na2PdCl4 and / or Na2PtCl4, wherein the liquid medium is an aqueous solvent, preferably water.

[0168] The amount of the transition metal compound provided in step (b) can vary and can be adjusted according to specific needs. According to one embodiment of the present invention, the amount of the transition metal compound provided in step (b) is in the range of 0.1 wt % to 20 wt %, preferably 0.1 wt % to 10 wt %, more preferably 0.2 wt % to 5 wt %, based on the weight of transition metal in the total weight of calcium carbonate reacted per surface.

[0169] The skilled person will appreciate that the transition metal compound provided in step (b) may be subjected to at least partial chemical transformation during any of the subsequent steps (c) to (e). In one embodiment, one or more reaction products obtained by the reaction of the transition metal compound with the surface-reacted calcium carbonate may thus be present in the mixture obtained in step (c) and / or in the concentrated mixture obtained in step (e) and / or in the product obtained in step (e).

[0170] Step (c): contacting the surface-reacted calcium carbonate with a transition metal compound

[0171] In step (c) of the production method according to the present invention, the surface-reacted calcium carbonate provided in step (a) is contacted with the transition metal compound provided in step (b) in a liquid medium to obtain a mixture comprising surface-reacted calcium carbonate and the transition metal compound.

[0172] Step (c) of contacting the surface-reacted calcium carbonate with a transition metal compound serves to impregnate at least part of the accessible surface of the surface-reacted calcium carbonate with the transition metal compound to provide a catalyst system having a transition metal compound on a solid support.

[0173] The contacting of the at least one surface-reacted calcium carbonate provided in step (a) with the at least one transition metal compound provided in step (b) can be accomplished by any conventional means known to the skilled person.

[0174] According to one embodiment of the present invention, step (c) comprises the following steps: providing at least one surface-reacted calcium carbonate provided in step (a) in a first step, and then adding at least one transition metal compound provided in step (b) in a subsequent step. According to another embodiment of the present invention, step (c) comprises the following steps: first providing at least one transition metal compound provided in step (b), and then adding at least one surface-reacted calcium carbonate provided in step (a). According to yet another embodiment, at least one surface-reacted calcium carbonate provided in step (a) and at least one transition metal compound provided in step (b) are provided and contacted simultaneously.

[0175] In case the at least one surface-reacted calcium carbonate provided in step (a) is provided as a first step, the at least one transition metal compound provided in step (b) may be added all at once or it may be added in several equal or unequal portions, i.e. in larger and smaller portions.

[0176] During the contacting step (c) of the process of the present invention, a mixture comprising the surface-reacted calcium carbonate of step (a) and the transition metal compound of step (b) is obtained. The mixture may be a suspension or slurry in a liquid medium.

[0177] In one embodiment of the process according to the invention, (i) the at least one surface-reacted calcium carbonate of step (a) is provided in the form of a suspension in a liquid medium; and / or (ii) the at least one transition metal compound of step (b) is provided in the form of a solution or suspension in a liquid medium, preferably in the form of a solution.

[0178] In a preferred embodiment, the surface-reacted calcium carbonate is provided as a suspension in a liquid medium, wherein the transition metal compound is also provided in the form of a solution or suspension in the liquid medium, preferably in the form of a solution.

[0179] As mentioned above, the surface-reacted calcium carbonate can be provided as a suspension or slurry in step (a), in which case the suspension or slurry comprises a suitable liquid medium. Typically, the liquid medium may be different from the liquid medium described herein as a suitable liquid medium for providing at least one transition metal compound in step (b) in solution or suspension form.

[0180] However, in a preferred embodiment, the liquid medium for providing the at least one surface-reacted calcium carbonate and the liquid medium for providing the at least one transition metal compound are the same.

[0181] The mixture obtained in step (c) may contain any liquid medium disclosed above, for example, the liquid medium may be a non-polar solvent, a polar solvent or a mixture thereof, preferably a non-polar solvent selected from pentane, cyclopentane, hexane, cyclohexane, benzene, toluene, 1,4-dihydrogen peroxide ... The mixture obtained in step (c) further comprises water, ethanol, ethanol / water mixture, toluene and mixtures thereof.

[0182] The contacting step (c) can be carried out by any means known in the art. For example, the at least one surface-reacted calcium carbonate of step (a) can be contacted with the transition metal compound of step (b) by spraying and / or mixing. Suitable devices for spraying or mixing are known to the skilled person.

[0183] According to one embodiment of the present invention, step (c) may be performed by spraying. Preferably, step (c) is performed by mixing.

[0184] The mixing in step (c) can be accomplished by any conventional means known to the skilled person. The skilled person will adjust the mixing conditions, such as mixing speed, separation and temperature, according to their process equipment. In addition, the mixing can be carried out under homogenization and / or particle separation conditions.

[0185] For example, mixing and homogenization can be performed by using a ploughshare mixer. The ploughshare mixer works by the principle of a fluidized bed produced mechanically. The ploughshare blades rotate close to the inner wall of a horizontal cylindrical drum, thereby transporting the components of the mixture out of the product bed and into the open mixing space. The fluidized bed ensures that even large batches are mixed vigorously in a very short time. In the case of a dry operating mode, a chopper and / or a disperser are used to disperse the agglomerates. Equipment that can be used for the method of the invention can be purchased commercially, for example from Germany or Germany

[0186] According to another embodiment of the present invention, step (c) is carried out for at least 1 second, preferably at least 1 minute (e.g. 10 minutes, 30 minutes or 60 minutes). According to a preferred embodiment, step (c) is carried out for a period of 1 second to 60 minutes, preferably a period of 15 minutes to 45 minutes. For example, mixing step (d) is carried out for 30 minutes ± 5 minutes.

[0187] Within the scope of the present invention, for example, in the case where the surface-reacted calcium carbonate is provided in dry form and the transition metal compound is provided in pure form or in the case where the intention is to adjust the solids content or the Brookfield viscosity of the mixture to a specific value, it is also possible to add a suitable liquid medium as described above during process step (c).

[0188] According to one embodiment of the present invention, the solid content of the mixture obtained in step (c) is in the range of 1 wt % to 90 wt %, preferably 3 wt % to 60 wt %, more preferably 5 wt % to 40 wt %, most preferably 10 wt % to 25 wt %, based on the total weight of the mixture.

[0189] Step (d): Removal of liquid medium

[0190] The process according to the present invention may optionally comprise a step (d) of removing the liquid medium from the mixture obtained in step (c).

[0191] As mentioned above, for example, if the at least one surface-reacted calcium carbonate in step (a) is provided as a suspension or slurry or if the at least one transition metal compound in step (b) is provided in the form of a solution or suspension, the mixture obtained in the contacting step (c) may contain a liquid medium. Furthermore, if the liquid medium is added during the contacting step (c), for example to adjust the solid content of the mixture, the mixture obtained in the contacting step (c) may contain a liquid medium to be removed in step (d).

[0192] Step (d) produces a concentrated mixture comprising less liquid medium than the mixture obtained in contacting step (c).In principle, the concentration step (d) can be accomplished by any conventional means known to the skilled person, for example by evaporating the liquid medium or by filtering.

[0193] Therefore, in one embodiment according to the present invention, at least part of the liquid medium comprised in the mixture of step (c) is removed by evaporation and / or by filtration.

[0194] The choice of method in step (d) may depend on the nature of the liquid medium contained in the mixture of step (c). For example, it may be preferred to remove aprotic solvents (e.g., toluene) by evaporation, while it may be preferred to remove protic solvents (e.g., ethanol or water) by filtration. In other cases, it may be preferred to combine initial filtration with subsequent evaporation of the residual liquid medium under reduced pressure (vacuum).

[0195] According to one embodiment of the present invention, the method of the present invention further comprises step (d): removing at least part of the liquid medium contained in the mixture of step (c) by evaporation. For example, the evaporation of the liquid medium can be carried out by applying heat and / or reduced pressure in an evaporator.

[0196] According to another embodiment of the present invention, the method of the present invention further comprises step (d): removing at least part of the liquid medium contained in the mixture of step (c) by filtration. For example, the filtration can be performed by a drum filter or a filter press or by nanofiltration.

[0197] According to yet another embodiment of the present invention, the process of the present invention further comprises a step (d): removing at least part of the liquid medium contained in the mixture of step (c) by filtration and evaporation, preferably by filtration and subsequent evaporation.

[0198] After removing at least part of the liquid medium contained in the mixture of step (c), the concentrated mixture obtained in step (d) is a concentrated mixture. In a preferred embodiment, the solid content of the concentrated mixture is at least 70% by weight, preferably at least 80% by weight, more preferably at least 85% by weight, and most preferably at least 90% by weight, based on the total weight of the mixture. For example, the solid content of the concentrated mixture can be 95% by weight, based on the total weight of the mixture.

[0199] According to yet another embodiment of the process of the present invention, the liquid medium contained in the mixture of step (c) is removed in step (d) to obtain a dried mixture.

[0200] Step (e): Heat treatment

[0201] According to step (e) of the process for producing the catalyst system of the present invention, the mixture of step (c) or the optional concentrated mixture of step (d) is subjected to a heat treatment at a temperature below 400°C, preferably at a temperature in the range of 170°C to 400°C, more preferably in the range of 200°C to 300°C, even more preferably in the range of 250 to 310°C, most preferably in the range of 280°C to 320°C.

[0202] The term "heating" does not limit the method according to the invention to a method in which the temperature of the mixture is actively adjusted to a defined temperature range by adding energy by an external heat source. The term also includes maintaining the temperature reached in an exothermic reaction (e.g. in contacting step (c)) for a specific period of time.

[0203] It is believed that the heat treatment performed in step (e) may further improve the performance of the catalyst system. For example, further improvements in catalytic activity, turnover rate or product yield may be observed. Further improvements in, for example, recovery of the catalyst system of the present invention and recycling in the second catalytic cycle or further catalytic cycles may also be observed.

[0204] The aforementioned advantages can be particularly pronounced if the heat treatment is carried out for a specific period of time. In one embodiment, step (e) is therefore carried out for at least 10 minutes, preferably 0.5 hours to 24 hours, more preferably 1 hour to 5 hours, most preferably 2.5 hours to 3.5 hours.

[0205] In a preferred embodiment, the mixture of step (c) or the optional concentrated mixture of step (d) is subjected to a heat treatment at a temperature below 400°C, preferably at a temperature in the range of 170°C to 400°C, more preferably 200°C to 300°C, even more preferably 250°C to 310°C, most preferably 280°C to 320°C, wherein the heat treatment is carried out for at least 10 minutes, preferably 0.5 hours to 24 hours, more preferably 1 hour to 5 hours, most preferably 2.5 hours to 3.5 hours.

[0206] Catalyst system

[0207] The catalyst system according to the present invention comprises a transition metal compound on a solid support, wherein the solid support is a surface-reacted calcium carbonate comprising ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) and at least one water-insoluble calcium salt other than calcium carbonate. The surface-reacted calcium carbonate is reacted with CO2 and one or more H3O + The reaction product of ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) treated with an ion donor and wherein CO2 is reacted with H3O + The ion donor process is formed in situ and / or supplied from an external source.

[0208] In general, the catalyst system of the present invention consists of a particulate solid support material (surface-reacted calcium carbonate) and a transition metal compound present on at least part of the accessible surface of the support material.

[0209] Specific embodiments of the surface-reacted calcium carbonate have been described above in step (a) of the process of the present invention and should be applied accordingly to the surface-reacted calcium carbonate of the catalyst system of the present invention.

[0210] For example, using phosphoric acid, H2PO4 - or HPO4 2- As H3O + The ion donor may result in the formation of hydroxyapatite. Thus, in a preferred embodiment, the at least one water-insoluble calcium salt is hydroxyapatite.

[0211] In a more preferred embodiment, the at least one water-insoluble calcium salt is hydroxyapatite, wherein the surface-reacted calcium carbonate provides a ratio of hydroxyapatite to calcite, aragonite and / or vaterite (preferably with calcite) by weight in the range of 1:99 to 99: 1. More preferably, the surface-reacted calcium carbonate provides a ratio of hydroxyapatite to calcite, aragonite and / or vaterite (preferably with calcite) by weight in the range of 1:9 to 9: 1, preferably 1:7 to 8: 1, more preferably 1:5 to 7: 1, most preferably 1:4 to 7: 1.

[0212] In a similar manner, use other H3O + The ion donor may result in the formation of a corresponding water-insoluble calcium salt other than calcium carbonate on at least part of the surface of the surface-reacted calcium carbonate. In one embodiment, the at least one water-insoluble calcium salt is therefore selected from octacalcium phosphate, hydroxyapatite, chlorapatite, fluorapatite, carbonapatite and mixtures thereof, wherein the surface-reacted calcium carbonate exhibits a ratio of at least one water-insoluble calcium salt relative to calcite, aragonite and / or vaterite (preferably with calcite) in the range of 1:99 to 99:1, preferably 1:9 to 9:1, more preferably 1:7 to 8:1, more preferably 1:5 to 7:1, most preferably 1:4 to 7:1 by weight.

[0213] The catalyst system according to the present invention further comprises a transition metal compound. Specific embodiments of the transition metal compound are also described above in step (b) and should be applied accordingly to the transition metal compound of the catalyst system.

[0214] In an exemplary embodiment, there is provided a transition metal compound catalyst system comprising a solid support, wherein the solid support is a surface-reacted calcium carbonate comprising ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) and at least one water-insoluble calcium salt other than calcium carbonate, and wherein the surface-reacted calcium carbonate exhibits:

[0215] (i) 15 m³ measured using nitrogen and the BET method according to ISO 9277:2010 2 / g to 200m 2 / g specific surface area;

[0216] (ii) The pore size at 0.1 cm calculated from mercury porosimetry measurements 3 / g to 2.3cm 3 / g range of intrusion specific pore volume within the particle; and

[0217] (iii) a ratio of at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite in the range of 1:99 to 99:1 by weight.

[0218] In another exemplary embodiment, the catalyst system according to the invention thus comprises a transition metal compound on a solid support, wherein the solid support is a surface-reacted calcium carbonate, the surface-reacted calcium carbonate being reacted with CO2 and one or more H3O + The reaction product of ion donor treated ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) wherein CO2 is reacted with H3O + The surface-reacted calcium carbonate comprises ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) and at least one water-insoluble calcium salt other than calcium carbonate, and wherein the surface-reacted calcium carbonate has:

[0219] (i) 15 m³ measured using nitrogen and the BET method according to ISO 9277:2010 2 / g to 200m 2 / g specific surface area;

[0220] (ii) The pore size at 0.1 cm calculated from mercury porosimetry measurements 3 / g to 2.3cm 3 / g range of intrusion specific pore volume within the particle; and

[0221] (iii) a ratio of at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite in the range of 1:99 to 99:1 by weight.

[0222] According to yet another exemplary embodiment, there is provided a catalyst system comprising a transition metal compound on a solid support, wherein the solid support is a surface-reacted calcium carbonate comprising ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) and at least one water-insoluble calcium salt other than calcium carbonate, wherein the surface-reacted calcium carbonate exhibits:

[0223] (i) 15 m³ measured using nitrogen and the BET method according to ISO 9277:2010 2 / g to 200m 2 / g specific surface area;

[0224] (ii) The pore size at 0.1 cm calculated from mercury porosimetry measurements 3 / g to 2.3cm 3 / g range of intrusion specific pore volume within the particle; and

[0225] (iii) a ratio of at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite in the range of 1:99 to 99:1 by weight.

[0226] And wherein the transition metal compound is selected from palladium compounds, platinum compounds, copper compounds and mixtures thereof, preferably the transition metal compound is a transition metal salt or a transition metal complex.

[0227] According to a further exemplary embodiment, the catalyst system according to the invention thus comprises a transition metal compound on a solid support, wherein the solid support is a surface-reacted calcium carbonate, the surface-reacted calcium carbonate being reacted with CO2 and one or more H3O + The reaction product of ion donor treated ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) wherein CO2 is reacted with H3O + The surface-reacted calcium carbonate is formed in situ by an ion donor treatment and / or supplied by an external source, the surface-reacted calcium carbonate comprising ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC) and at least one water-insoluble calcium salt other than calcium carbonate, wherein the surface-reacted calcium carbonate has:

[0228] (i) 15 m³ measured using nitrogen and the BET method according to ISO 9277:2010 2 / g to 200m 2 / g specific surface area;

[0229] (ii) The pore size at 0.1 cm calculated from mercury porosimetry measurements 3 / g to 2.3cm 3 / g range of intrusion specific pore volume within the particle; and

[0230] (iii) a ratio of at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite in the range of 1:99 to 99:1 by weight;

[0231] And wherein the transition metal compound is selected from palladium compounds, platinum compounds, copper compounds and mixtures thereof, preferably the transition metal compound is a transition metal salt or a transition metal complex.

[0232] In any of the foregoing exemplary embodiments, the transition metal compound may be preferably selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4, copper, Cu2O, Cu2S, copper(I)-thiophene-2-carboxylate, CuBr, CuCN, CuCl, CuF, CuI, CuH, CuSCN, CuBr2, Cu CO3, CuCl2, CuF2, Cu(NO3)2, Cu3(PO4)2, CuO, CuO2, Cu(OH)2, CuI2, CuS, CuSO4, Cu2(OAc)4 and mixtures thereof, preferably the transition metal compound is selected from elemental palladium, Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe) PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, elemental platinum, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4 and mixtures thereof.

[0233] The skilled person will appreciate that the transition metal compound provided in step (b) may be subjected to at least partial chemical transformation during any of the subsequent steps (c) to (e). In one embodiment, one or more reaction products obtained by the reaction of the transition metal compound with the surface-reacted calcium carbonate may thus be present in the mixture obtained in step (c) and / or in the concentrated mixture obtained in step (e) and / or in the product obtained in step (e).

[0234] Therefore, in one embodiment, the catalyst system further comprises one or more reaction products obtained by the reaction of a transition metal compound with surface-reacted calcium carbonate. In a preferred embodiment of the present invention, the one or more reaction products include bicarbonate, carbonate, hydroxide and oxide of the transition metal and monomeric forms of the transition metal.

[0235] The content of the transition metal compound and / or one or more reaction products thereof may be in the range of 0.1 wt % to 60 wt %, preferably 0.1 wt % to 30 wt %, more preferably 0.1 wt % to 20 wt %, even more preferably 0.1 wt % to 10 wt %, most preferably 0.2 wt % to 5 wt %, based on the weight of the transition metal compound per the total weight of the catalyst system.

[0236] Use of the catalyst system of the invention in heterogeneous catalysis

[0237] The catalyst system of the present invention has been found to be particularly useful in a number of catalytic reactions. For example, higher conversions in CC cross-coupling reactions and higher yields in glycerol hydrogenolysis have been achieved.

[0238] Therefore, one aspect of the present application relates to the use of the catalyst system of the present invention in a process comprising the following steps:

[0239] (a) providing one or more reactants;

[0240] (b) providing the catalyst system of the present invention;

[0241] (c) subjecting the one or more reactants provided in step (a) to a chemical reaction in the presence of the catalyst system provided in step (b).

[0242] Since it was found that the catalyst system of the present invention can be recovered more easily than conventional support systems and higher yields can be achieved in the second catalytic cycle, a preferred embodiment of the present invention relates to the use of the catalyst system of the present invention in a method according to the aforementioned aspects, wherein the method further comprises a step (d): recovering the catalyst system and recycling the transition metal after the chemical reaction of step (c). It should be understood that the term "recycling" covers recycling the transition metal in any form, including recycling of the complete catalyst system.

[0243] In a preferred embodiment of the present invention, the chemical reaction in step (c) comprises heterogeneous catalysis. In a more preferred embodiment, the chemical reaction in step (c) can be selected from one or more of the following reaction types: hydrogenolysis, CC coupling and CC cross coupling, CN cross coupling, CO cross coupling, CS cross coupling, cycloaddition reaction, olefin hydrogenation and alkyne hydrogenation, allyl substitution, reduction of nitro group and hydroformylation of aryl halide, preferably hydrogenolysis, CC coupling and CC cross coupling.

[0244] The catalyst system of the present invention can also be used in the form of pellets, moldings or extrudates comprising the catalyst system. Typical shapes include spheres, pellets, miniliths, honeycombs, rings and the like.

[0245] Granules are prepared by crushing and sieving the gel to obtain the desired size or by drying the precipitated paste with a binder. Optionally, the granulation process also includes heat treatment to achieve specific physical properties. The particle size of the granules is generally in the range of 40 μm to 1 cm.

[0246] A moulding is a hollow form having a specific shape obtained from something in a forgeable state.

[0247] Extrudates are formed by forcing the paste through a die, cutting to length, drying and optionally calcining. Example

[0248] A) Analytical methods

[0249] The parameters defined throughout this application and determined in the following examples are based on the following measurement methods:

[0250] Solid content

[0251] The solid content of the suspension (also called "dry weight") was determined using a moisture analyzer MJ33 (Mettler-Toledo, Switzerland) with the following settings: drying temperature 150°C, automatic switch-off if the mass does not change by more than 1 mg within 30 seconds, standard drying of 5 g of suspension.

[0252] Particle size distribution of granular materials

[0253] The particle size of the surface-reacted calcium carbonate herein is described as the volume-based particle size distribution d x The median particle size d was determined by volume using a Malvern Mastersizer 2000 laser diffraction system (Malvern Instruments Plc., Great Britain). 50 (volume) and volume-determined top cut particle size d 98 (Volume) for evaluation. 50 (volume) or d 98 The (volume) value represents the diameter value such that 50 volume % or 98 volume % of the particles have a diameter less than this value, respectively. The raw data obtained by the measurement are analyzed using Mie theory, where the particle refractive index is 1.57 and the absorption index is 0.005. This method and instrument are known to the skilled person and are commonly used to determine the particle size distribution of fillers and pigments.

[0254] The particle size of particulate materials other than surface-reacted calcium carbonate is described herein as a particle size distribution based on weight. x(volume). Median particle size determined by weight by sedimentation method d 50 (weight), sedimentation method is the analysis of sedimentation behavior in a weight field. TM The measurement is performed using a 5100 or 5120. The method and instrument are known to the skilled person and are commonly used to determine the particle size distribution of fillers and pigments. The measurement is performed in an aqueous solution of 0.1 wt. % Na4P2O7. The sample is dispersed and sonicated using a high-speed stirrer.

[0255] Porosity determination

[0256] The specific pore volume was measured using mercury intrusion porosimetry using a Micromeritics Autopore V 9620 mercury porosimeter with a maximum applied pressure of 414 MPa (60,000 psi) of mercury (equivalent to a Laplace throat diameter of 0.004 μm (~nm)). The equilibrium time used for each pressure step was 20 seconds. The sample material was sealed in a 3 cm 3 The data were corrected for mercury compression, penetrometer expansion, and sample material compression using the software Pore-Comp (Gane, PAC, Kettle, JP, Matthews, GP, and Ridgway, CJ, "Void Space Structure of Compressible Polymer Spheres and Consolidated Calcium Carbonate Paper-Coating Formulations", Industrial and Engineering Chemistry Research, 35(5), 1996, pp. 1753-1764).

[0257] The total pore volume seen in the cumulative intrusion data can be divided into two regions, where the intrusion data from 214 μm down to about 1 μm to 4 μm shows that the coarse packing between any agglomerate structures of the sample plays an important role. Smaller than these diameters is the fine inter-particle packing of the particles themselves. If they also have intra-particle pores, this region appears bimodal, and by taking the specific pore volume in pores finer than the inflection point of the peak (i.e., finer than the inflection point of the bimodal) intruded by mercury, we thereby define the specific intra-particle pore volume. The sum of these three regions gives the total overall pore volume of the powder, but is strongly dependent on initial sample compaction / settling of the powder at the coarse pore end of the distribution.

[0258] By taking the first derivative of the cumulative intrusion curve, the pore size distribution based on the equivalent Laplace diameter is revealed (inevitably including pore shielding). The differential curve clearly shows the coarse agglomerate pore structure region, the inter-particle pore region, and the intra-particle pore region (if present). Knowing the intra-particle pore diameter range, the remaining inter-particle pore volume and the inter-agglomerate pore volume can be subtracted from the total pore volume to provide the desired pore volume of the internal pores alone, in terms of pore volume per unit mass (specific pore volume). Of course, the same subtraction principle applies to separating any other pore size regions of interest.

[0259] BET specific surface area (SSA) of the material

[0260] Throughout this document, the specific surface area (in m2) of surface-reacted calcium carbonate or other materials is determined using the BET method (using nitrogen as adsorption gas) which is well known to the skilled person (ISO 9277:2010). 2 The total surface area (in m2) of the filler material was then obtained by multiplying the specific surface area and mass (in g) of the corresponding sample. 2 count).

[0261] X-ray diffraction (XRD)

[0262] XRD experiments were performed on the samples using a rotatable PMMA holding ring. The samples were analyzed using a Bruker D8Advance powder diffractometer that follows Bragg's law. The diffractometer consists of a 2.2 kW X-ray tube, a sample holder, a θ-θ goniometer, and a Detector composition. Nickel-filtered Cu Kα radiation was used in all experiments. Profiles were automatically recorded using a scan rate of 0.7° / min in 2θ. The resulting powder diffraction patterns can be easily classified by mineral content using the DIFFRACsuite software packages EVA and SEARCH based on reference patterns from the ICDD PDF 2 database.

[0263] Quantitative analysis of diffraction data refers to determining the amounts of different phases in a multiphase sample and has been performed using the DIFFRACsuite software package TOPAS. In detail, quantitative analysis allows structural features and phase proportions to be determined with quantifiable numerical accuracy from the experimental data themselves. This involves modeling the full diffraction pattern using the Rietveld method so that the calculated pattern is consistent with the experimental pattern.

[0264] HPLC chromatography

[0265] Suzuki reaction: A Dionex P680 HPLC pump (1.0 ml min) equipped with a Dionex UVD3400 detector, a Dionex Asi-100 autosampler (10 μL injection), a Dionex TCC-100 HPLC column thermostat (40 °C), and a DG1210 degasser was used. -1 ) in Waters Symmetry Shield TM The samples were analyzed on a column (RP-8, 3.5 M, 4.6 x 50 mM). A gradient from 0% to 100% acetonitrile in aqueous phase (0.1% formic acid and 5% acetonitrile in demineralized water) was used as eluent.

[0266] Hydrogenolysis: The reaction was carried out using a Dionex P680 HPLC pump (0.8 mL min) equipped with an ERC RefractoMax 520 detector, a Dionex Asi-100 autosampler (10 μL injection), and a Dionex TCC-100 HPLC column thermostat (70 °C). -1 ) in Waters Symmetry Shield TM The samples were analyzed on a column (RP-8, 3.5 M, 4.6 x 50 mM) using 5 mM H2SO4 (pH 1.5) in demineralized water as eluent.

[0267] B) Preparation of carrier (MCC)

[0268] SRCC1(d 50 (volume) = 4.4 μm, d 98 (Volume) = 8.6 μm, SSA = 39.9 m 2 g -1 )

[0269] SRCC1 was obtained as follows: 10 liters of an aqueous suspension of ground calcium carbonate was prepared in a mixing vessel by adjusting the solids content of ground marble calcium carbonate from Hustadmarmor, Norway, with a mass-based particle size distribution of 90% less than 2 μm (as determined by sedimentation) so as to obtain a solids content of 15% by weight, based on the total weight of the aqueous suspension. In addition, a solution containing 30% by weight of phosphoric acid was prepared. While mixing the slurry, 0.83 kg of phosphoric acid solution was added to the suspension at a temperature of 70° C. over a period of 10 minutes. Finally, after the addition of the phosphoric acid, the slurry was stirred for a further 5 minutes before being removed from the vessel, filtered and dried.

[0270] SRCC2(d 50 (volume) = 8.3 μm, d 98 (Volume) = 19.5 μm, SSA = 74.4 m 2 g -1 )

[0271] SRCC2 was obtained as follows: 10 liters of an aqueous suspension of ground calcium carbonate was prepared in a mixing vessel by adjusting the solids content of ground marble calcium carbonate from Hustadmarmor, Norway, with a mass-based particle size distribution of 90% less than 2 μm (as determined by sedimentation) so as to obtain a solids content of 15% by weight based on the total weight of the aqueous suspension. In addition, a solution was prepared by blending dilute phosphoric acid and aluminum sulfate hexahydrate, wherein the concentration of phosphoric acid was 30% by weight, and aluminum sulfate hexahydrate was added at 5% by mass of the mass of pure phosphoric acid. While mixing the slurry, 1.7 kg of phosphoric acid / aluminum sulfate solution was added to the suspension at a temperature of 70° C. over a period of 10 minutes. Finally, after the addition of the phosphoric acid, the slurry was stirred for a further 5 minutes before being removed from the container, filtered and dried.

[0272] SRCC3(d 50 (volume) = 8.2 μm, d 98 (Volume) = 16.7 μm, SSA = 90.0 m 2 g -1 )

[0273] SRCC3 was obtained as follows: 10 liters of an aqueous suspension of ground calcium carbonate was prepared in a mixing vessel by adjusting the solids content of ground marble calcium carbonate from Hustadmarmor, Norway, with a mass-based particle size distribution of 90% less than 2 μm (as determined by sedimentation) so as to obtain a solids content of 10% by weight based on the total weight of the aqueous suspension. In addition, a solution was prepared by blending dilute phosphoric acid and citric acid, wherein the concentration of phosphoric acid was 29% by weight, and citric acid was added at 10% by mass of the mass of pure phosphoric acid. While mixing the slurry, 1.65 kg of phosphoric acid / citric acid solution was added to the suspension at a temperature of 70° C. over a period of 10 minutes. Finally, after the addition of the phosphoric acid, the slurry was stirred for a further 5 minutes before being removed from the container, filtered and dried.

[0274] SRCC4(d 50 (volume) = 6.7 μm, d 98 (Volume) = 12.9 μm, SSA = 146.5 m 2 g -1 )

[0275] SRCC4 was obtained as follows: 10 1 of an aqueous suspension of ground calcium carbonate was prepared in a mixing vessel by adjusting the solids content of ground marble calcium carbonate from Hustadmarmor, Norway, with a mass-based particle size distribution of 90% less than 2 μm (as determined by sedimentation) so as to obtain a solids content of 10 wt.-% based on the total weight of the aqueous suspension. In addition, a solution containing 30 wt.-% phosphoric acid was prepared, while another solution containing 5 wt.-% citric acid was prepared. While the slurry was being mixed, 1.60 kg of phosphoric acid solution was added to the suspension at a temperature of 70° C. over a period of 10 minutes. In addition, 0.05 kg of citric acid solution was also added to the slurry starting 2 minutes after the start of the phosphoric acid addition. Finally, after the addition of the phosphoric acid, the slurry was stirred for a further 5 minutes before being removed from the vessel, filtered and dried.

[0276] SRCC5(d 50 (volume) = 7.1 μm, d 98 (Volume) = 13.5 μm, SSA = 119.2 m 2 g -1 )

[0277] SRCC5 was obtained as follows: 10 liters of an aqueous suspension of ground calcium carbonate was prepared in a mixing vessel by adjusting the solids content of ground marble calcium carbonate from Hustadmarmor, Norway, with a mass-based particle size distribution of 90% less than 2 μm (as determined by sedimentation) so as to obtain a solids content of 10% by weight based on the total weight of the aqueous suspension. In addition, a solution containing 30% by weight of phosphoric acid was prepared, while another solution containing 5% by weight of citric acid was prepared. While mixing the slurry, 1.60 kg of phosphoric acid solution was added to the suspension at a temperature of 70° C. over a period of 10 minutes. In addition, 0.05 kg of citric acid solution was also added to the slurry starting 3 minutes after the start of the phosphoric acid addition. Finally, after the addition of the phosphoric acid, the slurry was stirred for a further 5 minutes before being removed from the container, filtered and dried.

[0278] Table 1: Quantitative Rietveld analysis (XRD) of supports (data normalized to 100% crystalline material).

[0279] mineral Mode SRCC1 SRCC2 SRCC3 SRCC4 SRCC5 Calcite <![CDATA[CaCO3]]> 74.5 50.6 17.7 14.7 16.9 Hydroxyapatite <![CDATA[Ca5(OH)(PO4)3]]> 25.5 49.4 82.3 85.3 83.1 total 100 100 100 100 100

[0280] Table 2: Hg porosimetry of supports.

[0281]

[0282] a) For pore sizes ranging from 0.004 μm to 0.18 μm

[0283] b) For pore sizes ranging from 0.004 μm to 0.32 μm

[0284] c) For pore sizes ranging from 0.004 μm to 0.9 μm

[0285] d) For pore sizes ranging from 0.004 μm to 0.51 μm

[0286] e) For pore sizes ranging from 0.004 μm to 0.51 μm

[0287] C) Preparation of Catalyst

[0288] Method 1: Non-aqueous immersion in ethanol

[0289] A slurry of the support (0.5 g) was prepared in an organic solvent (20 ml) in which the metal salt had been dissolved. The slurry was then stirred (18 hours) and filtered, and dried under vacuum at ambient temperature for 18 hours. This process could be repeated once to increase the catalyst loading.

[0290] Method 2: Non-aqueous immersion in toluene

[0291] A slurry of the support (2 g) was prepared in an organic solvent (25 ml) in which a metal salt was also dissolved. The solvent was then evaporated under constant stirring to impregnate the catalyst onto the support and obtain a uniform powder. The material was then dried under vacuum at ambient temperature for 18 hours and calcined at 300°C.

[0292] Method 3: Water-based Dipping

[0293] First, the water-soluble metal salt is dissolved in water (4 ml) and the pH is adjusted to 5.5 to 6 by using NaHCO3 (saturated). The solution is added to a slurry of the support (1.8 g to 2.0 g) in water (8 ml to 12 ml). The mixture is heated to 70 ° C, kept for 30 minutes to 90 minutes, and then cooled to room temperature. The catalyst is filtered out, rinsed with water (3×4 ml), vacuum dried at ambient temperature for 18 hours, and then calcined at 300 ° C for 3 hours. This process can be repeated several times to increase the catalyst loading.

[0294] Table 3: Prepared catalysts (C1 to C20)

[0295]

[0296] a) Catalyst amount used for impregnation (wt% Pd or Pt)

[0297] Evaluation of catalyst loading:

[0298] The filtrate solution from the aqueous impregnation of C19 (SRCC4) was allowed to stand until all soluble metal salts precipitated as a black material (i.e. until the solution was completely decolorized). The precipitate was weighed and the catalyst loading was calculated in reverse from this value to be 4.6 wt% Pt. This calculation was made based on metallic platinum.

[0299] D) Application examples

[0300] Suzuki reaction (Examples A1 to A10, Comparative Examples CA1 to CA5)

[0301] According to Letters in Organic Chemistry, 4, 2007, 13-15, various catalyst loadings and catalyst types are used to carry out the coupling reaction between iodobenzene and phenylboronic acid. In a typical reaction, 0.45 g phenylboronic acid (1.5 equivalents, 3.7 mmol) is weighed in a 100 ml round-bottom flask. Potassium carbonate (2.9 equivalents, 7.3 mmol, 1.0 g) is added to the mixture together with 80 mL of solvent (40% ethanol in water). Flask is closed with diaphragm, stirring is started and flask is purged with nitrogen stream. Then iodobenzene (0.50 g, 2.5 mmol) is added, followed by addition of pre-weighed catalyst (in a closed vial). Nitrogen purge is continued for 10 minutes to 15 minutes. From mixture, aliquots (about 0.5 ml) are taken out at regular intervals, extracted with 1 ml of heptane and analyzed by the HPLC using a UV diode array detector (238 nm). Conversion efficiency is summarized in Table 4.

[0302] At the end of the reaction, heptane was added to the reaction mixture and stirred for about 15 minutes, then the contents were transferred to a 250 ml separatory funnel and the phases were separated, and the organic phase was dried for about 12 hours and filtered over Na2SO4. The clarified organic layer was concentrated to dryness in a tared round-bottomed flask using a rotary evaporator. The round-bottomed flask was weighed to determine the yield of the reaction. A porous glass filter (porosity 3) was used to separate the aqueous layer from the extract containing the catalyst by vacuum filtration. The filter cake was washed with deionized water, ethanol and heptane. The filter containing the filter cake was placed in a vacuum oven and dried under complete vacuum at 20°C for >24 hours. After drying, the dried catalyst was collected from the filter and weighed into a screw cap glass vial to determine the amount of catalyst recovered.

[0303] Table 4: Comparison at catalyst loadings similar to commercial supported catalysts.

[0304]

[0305] a) Based on iodobenzene

[0306] Table 4 above shows the improved efficiency of the catalyst prepared according to the present invention relative to the commercial Pd / CaCO3 catalyst. The catalyst preparation can be seen in Table 3.

[0307] Table 5: Recyclability of catalysts.

[0308]

[0309] a) The recovered catalyst from the 1st catalytic cycle (tests using 1% and 0.6% catalyst) was combined and used in the 2nd catalytic cycle.

[0310] #)No experiments were performed.

[0311] Table 5 above shows good efficiency of the recovered catalysts and they are easier to recover than the commercial catalysts from the commercial samples.

[0312] Hydrogenolysis of glycerol (Examples A11 to A21)

[0313] React according to Catalysis Communications, 13, 2011, 1-5. A mixture of catalyst (5 mol% active metal, relative to glycerol) and 20ml glycerol (100mM) in water was placed under 40 bar hydrogen pressure and then heated to 200°C for 18 hours while stirring at 800rpm. After cooling to room temperature, sampling was performed for analysis. The sample was filtered and mixed with an equal amount of 5mM H2SO4. The catalyst was filtered out, rinsed with water (3×1ml) and dried under vacuum. The reaction mixture was analyzed by HPLC to determine the amount of starting material (glycerol) and 4 main reaction products (lactic acid (LA), 1,2-propylene glycol (12-PD), ethylene glycol (EG) and ethanol (EtOH)). In all cases, these compounds accounted for ≥95% of the total peak area. The results are summarized in Table 6.

[0314] Table 6: Examples A11 to A20 and CA6 (hydrogenolysis of glycerol)

[0315]

[0316] a) Determined by HPLC analysis after reaction (% of peak area to total peak area)

[0317] Table 6 shows that all catalysts according to the present invention exhibited higher activities than the commercial catalyst used as comparative example.

Claims

1. A catalyst system for catalyzing a glycerol hydrogenolysis reaction and / or a CC cross-coupling reaction, comprising a transition metal compound on a solid support, wherein the solid support is a surface-reacted calcium carbonate, the surface-reacted calcium carbonate comprises ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC), and at least one water-insoluble calcium salt other than calcium carbonate, and wherein the surface-reacted calcium carbonate exhibits: (i) 15 m³ measured using nitrogen and the BET method according to ISO 9277:2010 2 / g to 200m 2 / g specific surface area; (ii) The pore size at 0.1 cm calculated from mercury porosimetry measurements 3 / g to 2.3cm 3 / g range of intrusion specific pore volume within the particle; and (iii) a ratio of the at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite in the range of 1:99 to 99:1 by weight, wherein the transition metal is selected from palladium, platinum and mixtures thereof, and the transition metal compound is a molecular transition metal compound, a transition metal salt, a metallic transition metal compound, or a transition metal complex, and wherein the at least one water-insoluble calcium salt is defined as a material that, when 100 g of the material is mixed with 100 g of deionized water and filtered at 20° C. on a filter having a pore size of 0.2 μm to recover a liquid filtrate, provides less than or equal to 1 g of recovered solid material upon evaporation of 100 g of the liquid filtrate at 95° C. to 100° C. at ambient pressure, wherein the catalyst system further comprises one or more reaction products obtained by the reaction of the transition metal compound with the surface-reacted calcium carbonate.

2. The catalyst system according to claim 1, wherein the at least one water-insoluble calcium salt is selected from the group consisting of octacalcium phosphate, hydroxyapatite, chloroapatite, fluoroapatite, carbonapatite and mixtures thereof.

3. The catalyst system of claim 1, wherein the at least one water-insoluble calcium salt is hydroxyapatite.

4. The catalyst system according to any one of claims 1 to 3, wherein the ratio of the at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite is in the range of 1:9 to 9:1 by weight.

5. The catalyst system according to any one of claims 1 to 3, wherein the ratio of the at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite is in the range of 1:7 to 8:1 by weight.

6. The catalyst system according to any one of claims 1 to 3, wherein the ratio of the at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite is in the range of 1:5 to 7:1 by weight.

7. The catalyst system according to any one of claims 1 to 3, wherein the ratio of the at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite is in the range of 1:4 to 7:1 by weight.

8. The catalyst system according to any one of claims 1 to 3, wherein the ratio of the at least one water-insoluble calcium salt to calcite is in the range of 1:9 to 9:1 by weight.

9. The catalyst system according to any one of claims 1 to 3, wherein the ratio of the at least one water-insoluble calcium salt to calcite is in the range of 1:7 to 8:1 by weight.

10. The catalyst system according to any one of claims 1 to 3, wherein the ratio of the at least one water-insoluble calcium salt to calcite is in the range of 1:5 to 7:1 by weight.

11. The catalyst system according to any one of claims 1 to 3, wherein the ratio of the at least one water-insoluble calcium salt to calcite is in the range of 1:4 to 7:1 by weight.

12. The catalyst system according to any one of claims 1 to 3, wherein the transition metal compound is selected from the group consisting of palladium compounds, platinum compounds and mixtures thereof.

13. The catalyst system according to any one of claims 1 to 3, wherein the transition metal compound is selected from Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4, and mixtures thereof.

14. The catalyst system according to any one of claims 1 to 3, wherein the surface-reacted calcium carbonate has: (i) Measured at 27 m using nitrogen and the BET method according to ISO 9277:2010 2 / g to 180m 2 Specific surface area in the range of / g; (ii) d in the range of 1 μm to 75 μm 50 (volume); (iii) d in the range of 2 μm to 150 μm 98 (volume); and / or (iv) The pore size at 0.2 cm calculated from mercury porosimetry measurements 3 / g to 2.0cm 3 / g range of intrusion specific pore volume within the particles.

15. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (i) Measured at 25 m using nitrogen and the BET method according to ISO 9277:2010 2 / g to 160m 2 / g range of specific surface area.

16. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (i) Measured at 30 m using nitrogen and the BET method according to ISO 9277:2010 2 / g to 150m 2 / g range of specific surface area.

17. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (ii) d in the range of 2 μm to 50 μm 50 (volume).

18. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (ii) d in the range of 3 μm to 40 μm 50 (volume).

19. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (ii) d in the range of 4 μm to 30 μm 50 (volume).

20. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (ii) d in the range of 5 μm to 15 μm 50 (volume).

21. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (iii) d in the range of 4 μm to 100 μm 98 (volume).

22. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (iii) d in the range of 6 μm to 80 μm 98 (volume).

23. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (iii) d in the range of 8 μm to 60 μm 98 (volume).

24. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (iii) d in the range of 10 μm to 30 μm 98 (volume).

25. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (iv) The pore size at 0.4 cm calculated from mercury porosimetry measurements 3 / g to 1.8cm 3 / g range of intra-particle intrusion specific pore volume.

26. The catalyst system of claim 14, wherein the surface-reacted calcium carbonate has: (iv) The pore size at 0.6 cm calculated from mercury porosimetry measurements 3 / g to 1.6cm 3 / g range of intra-particle intrusion specific pore volume.

27. The catalyst system according to any one of claims 1 to 3, wherein the content of the transition metal compound and / or one or more reaction products thereof is in the range of 0.1 wt% to 60 wt%, based on the weight of the transition metal compound / total weight of the catalyst system.

28. The catalyst system according to any one of claims 1 to 3, wherein the content of the transition metal compound and / or one or more reaction products thereof is in the range of 0.1 wt% to 30 wt%, based on the weight of the transition metal compound / total weight of the catalyst system.

29. The catalyst system according to any one of claims 1 to 3, wherein the content of the transition metal compound and / or one or more reaction products thereof is in the range of 0.1 wt% to 20 wt%, based on the weight of the transition metal compound / total weight of the catalyst system.

30. The catalyst system according to any one of claims 1 to 3, wherein the content of the transition metal compound and / or one or more reaction products thereof is in the range of 0.1 wt% to 10 wt%, based on the weight of the transition metal compound / total weight of the catalyst system.

31. The catalyst system according to any one of claims 1 to 3, wherein the content of the transition metal compound and / or one or more reaction products thereof is in the range of 0.2 wt% to 5 wt%, based on the weight of the transition metal compound / total weight of the catalyst system.

32. A method for preparing a catalyst system for catalyzing a glycerol hydrogenolysis reaction and / or a CC cross-coupling reaction, the catalyst system comprising a transition metal compound on a solid support, the method comprising the steps of: (a) providing at least one surface-reacted calcium carbonate, the surface-reacted calcium carbonate comprising ground natural calcium carbonate (GNCC) or precipitated calcium carbonate (PCC), and at least one water-insoluble calcium salt other than calcium carbonate; (b) providing at least one transition metal compound; and (c) contacting the surface-reacted calcium carbonate provided in step (a) with the transition metal compound provided in step (b) in a liquid medium to obtain a mixture comprising surface-reacted calcium carbonate and a transition metal compound; wherein the surface-reacted calcium carbonate exhibits: (i) 15 m³ measured using nitrogen and the BET method according to ISO 9277:2010 2 / g to 200m 2 / g specific surface area; (ii) The pore size at 0.1 cm calculated from mercury porosimetry measurements 3 / g to 2.3cm 3 / g range of intrusion specific pore volume within the particle; and (iii) a ratio of the at least one water-insoluble calcium salt to calcite, aragonite and / or vaterite in the range of 1:99 to 99:1 by weight, wherein the transition metal is selected from palladium, platinum and mixtures thereof, and the transition metal compound is a molecular transition metal compound, a transition metal salt, a metallic transition metal compound, or a transition metal complex, and wherein the at least one water-insoluble calcium salt is defined as a material that, when 100 g of the material is mixed with 100 g of deionized water and filtered at 20° C. on a filter having a pore size of 0.2 μm to recover a liquid filtrate, provides less than or equal to 1 g of recovered solid material upon evaporation of 100 g of the liquid filtrate at 95° C. to 100° C. at ambient pressure, wherein the catalyst system further comprises one or more reaction products obtained by the reaction of the transition metal compound with the surface-reacted calcium carbonate.

33. The method of claim 32, wherein (i) the at least one surface-reacted calcium carbonate of step (a) is provided in the form of a suspension in a liquid medium; and / or (ii) The at least one transition metal compound of step (b) is provided in the form of a solution or suspension in a liquid medium.

34. The method of claim 33, wherein (ii) The at least one transition metal compound of step (b) is provided in the form of a solution in a liquid medium.

35. The method according to any one of claims 32 to 34, wherein the method further comprises a step (d) of removing at least a portion of the liquid medium contained in the mixture of step (c) by evaporation and / or filtration to obtain a concentrated mixture.

36. The method according to any one of claims 32 to 34, wherein the method further comprises the step (e) of heat treating the mixture of step (c) or the concentrated mixture of step (d) at a temperature below 400°C.

37. The method according to any one of claims 32 to 34, wherein the method further comprises the step (e): heat treating the mixture of step (c) or the concentrated mixture of step (d) at a temperature in the range of 170°C to 400°C.

38. The method according to any one of claims 32 to 34, wherein the method further comprises the step (e) of heat treating the mixture of step (c) or the concentrated mixture of step (d) at a temperature in the range of 200°C to 300°C.

39. The method according to any one of claims 32 to 34, wherein the method further comprises the step (e): heat treating the mixture of step (c) or the concentrated mixture of step (d) at a temperature in the range of 250°C to 310°C.

40. The method according to any one of claims 32 to 34, wherein the method further comprises the step (e) of heat treating the mixture of step (c) or the concentrated mixture of step (d) at a temperature in the range of 280°C to 320°C.

41. The method of any one of claims 32 to 34, wherein the transition metal compound is selected from palladium compounds, platinum compounds, and mixtures thereof.

42. The method of any one of claims 32 to 34, wherein the transition metal compound is selected from the group consisting of Pd(acac)2, Na2PdCl4, Pd(OAc)2, Pd(PPh3)4, PdCl2(PPh3)2, (dppf)PdCl2, (dppe)PdCl2, (dppp)PdCl2, (dppb)PdCl2, PdCl2, (C3H5PdCl)2, bis(acetate)triphenylphosphine-palladium(II), Pd(dba)2, Pd(H2NCH2CH2NH2)Cl2, Na2PtCl6Pt(acac)2, Na2PtCl4, H2PtCl6, (NH4)2[PtCl6], PtO2·H2O, PtCl4, and mixtures thereof.

43. The method of any one of claims 32 to 34, wherein the liquid medium is a non-polar solvent, a polar solvent, or a mixture thereof.

44. The method of claim 43, wherein the non-polar solvent is selected from the group consisting of pentane, cyclopentane, hexane, cyclohexane, benzene, toluene, 1,4-dihydrogen peroxide, The polar solvent is selected from tetrahydrofuran, ethyl acetate, acetone, dimethylformamide, acetonitrile, dimethyl sulfoxide, nitromethane, propylene carbonate, formic acid, n-butanol, isopropanol, n-propanol, ethanol, methanol, acetic acid, water and a mixture thereof.

45. A method according to any one of claims 32 to 34, wherein the transition metal compound is Na2PdCl4 and / or Na2PtCl4, and the liquid medium is a polar solvent; and / or the transition metal compound is Pd(acac)2 and / or Pt(acac)2, and the liquid medium is a non-polar solvent.

46. ​​The method of claim 45, wherein the polar solvent is water.

47. The method of claim 45, wherein the non-polar solvent is toluene.

48. Use of a catalyst system according to any one of claims 1 to 31 in a process comprising the steps of: (a) providing one or more reactants; (b) providing a catalyst system according to any one of claims 1 to 31; (c) subjecting the one or more reactants provided in step (a) to a chemical reaction in the presence of the catalyst system provided in step (b); (d): recovering the catalyst system and recycling the transition metal after the chemical reaction of step (c); The chemical reaction in step (c) is selected from one or more of the following reaction types: glycerol hydrogenolysis and CC cross-coupling.

49. Use of the surface-reacted calcium carbonate as defined in any one of claims 1 to 11 or 14 to 26 as a support for a transition metal-based catalyst, wherein the transition metal is selected from: palladium, platinum and mixtures thereof, and the transition metal compound is a molecular transition metal compound, a transition metal salt, a metallic transition metal compound, or a transition metal complex.

50. Pellets, moldings or extrudates comprising the catalyst system according to any one of claims 1 to 31.

Citation Information

Patent Citations

  • Process to prepare a surface-reacted calcium carbonate implementing a weak acid, resulting products and uses thereof

    EP2264108A1

  • Process for preparing surface-reacted calcium carbonate and its use

    EP2264109A1

  • Process for obtaining precipitated calcium carbonate

    EP2371766A1

  • Production of high purity precipitated calcium carbonate

    EP2447213A1

  • Precipitated calcium carbonate from pulp mill waste having an improved brightness, method for the production and use thereof

    EP2524898A1